Thin gauge aluminum-based cathode for lithium ion battery

By using thin specifications of 1xxx series or 8xxx series aluminum alloy to manufacture the cathode current collector of lithium-ion batteries, the problem of short cycle life of existing batteries is solved, and the effect of maintaining high specific capacity and energy density under high cycle times is achieved.

CN119968720APending Publication Date: 2025-05-09NOVELIS INC(US)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380062585.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-01
Filing Date
2023-08-31
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

The cathode current collector thickness of existing lithium-ion batteries leads to a short cycle life of the battery and it is difficult to maintain high efficiency of specific capacity and energy density under high cycle times.

Method used

The cathode current collector is made of thin specifications 1xxx series or 8xxx series aluminum alloys, with a thickness ranging from 5 μm to 12 μm. Combined with the design of the active material layer and the conductive layer, the conductivity and bond strength of the cathode current collector are optimized.

Benefits of technology

It significantly extends the cycle life of the battery and can maintain more than 90% of the specific capacity and energy density within up to 3000 cycles, improving the energy density and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119968720A_ABST
    Figure CN119968720A_ABST
Patent Text Reader

Abstract

Batteries and battery components are described that include a cathode current collector comprising an aluminum alloy of the 1xxx series or an aluminum alloy of the 8xxx series. The cathode current collector may have a thickness of 5 [mu] m to 12 [mu] m. In some examples, a cathode active material layer may be disposed on at least a portion of the cathode current collector. The cathode current collector may have two surfaces as matte surfaces in contact with the active material layer. Comprising the cathode current collector can maintain a specific capacity above 90% of an initial specific capacity over up to 3000 cycles or more cycles. In addition, the battery cell including the cathode current collector may maintain an energy density above 90% of an initial energy density over up to 3000 cycles or more cycles.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of and priority to U.S. Provisional Application No. 63 / 374,283, filed on September 1, 2022, which is incorporated herein by reference in its entirety. Technical Field

[0003] The present disclosure relates generally to metallurgy and, more particularly, to improving battery current collectors and other components using thin gauge aluminum alloys, such as 1xxx series aluminum alloys or 8xxx series aluminum alloys. Background Art

[0004] Conventional lithium-ion batteries typically include a cathode, an anode, and a separator therebetween that is impregnated with an electrolyte. Current collectors on the cathode and anode sides are used to conduct current between the cathode and anode, while the electrolyte allows lithium ions to be transported between the cathode and anode. Due to the potentials involved, copper is typically used as the anode current collector, and aluminum is typically used as the cathode current collector. Lithium metal oxides, such as lithium cobalt oxide, are often used as lithium-ion battery cathodes, while graphite is often used as lithium-ion battery anodes. Summary of the invention

[0005] The term embodiment and similar terms are intended to refer broadly to the subject matter of the present disclosure and the entirety of the following claims. Statements containing these terms should not be understood to limit the subject matter described herein, or to limit the meaning or scope of the following claims. The embodiments of the present disclosure covered herein are defined by the following claims rather than by this disclosure. This disclosure is a high-level overview of various aspects of the present disclosure and introduces some concepts that are further described in the following detailed description section. This disclosure is neither intended to identify the key or essential features of the claimed subject matter nor is it intended to be used independently to determine the scope of the claimed subject matter. The subject matter should be understood by reference to appropriate portions of the entire specification of the present disclosure, any or all drawings, and each claim.

[0006] Battery components are described herein. An example battery component includes a cathode current collector comprising a 1xxx series aluminum alloy or an 8xxx series aluminum alloy. The cathode current collector may have a thickness of 5 μm to 12 μm. Optionally, the cathode current collector may have a thickness of 7 μm to 10 μm. Example thicknesses may include 5 μm to 5.1 μm, 5.1 μm to 5.2 μm, 5.2 μm to 5.3 μm, 5.3 μm to 5.4 μm, 5.4 μm to 5.5 μm, 5.5 μm to 5.6 μm, 5.6 μm to 5.7 μm, 5.7 μm to 5.8 μm, 5.8 μm to 5.9 μm, 5.9 μm to 6.0 μm, 6.0 μm to 6.1 μm, 6.1 μm to 6.2 μm, 6.2 μm to 6.3 μm, 6.3 μm to 6.4 μm, 6.4 μm to 6.5 μm, 6.5 μm to 6.6 μm, 6.6 μm to 6.7 μm, 6.7 μm to 6.8 μm. .8μm, 6.8μm to 6.9μm, 6.9μm to 7.0μm, 7μm to 7.1μm, 7.1μm to 7.2μm, 7.2μm to 7.3μm, 7.3μm to 7.4μm, 7.4μm to 7.5μm, 7.5μm to 7.6μm, 7.6μm to 7.7μm, 7.7μm to 7.8μm, 7.8μm to 7.9μm, 7.9μm to 8μm, 8μm to 8.1μm, 8.1μm to 8.2μm, 8.2μm to 8.3μm, 8.3μm to 8.4μm, 8.4μm to 8.5μm, 8.5μm to 8.6μm, 8. 6μm to 8.7μm, 8.7μm to 8.8μm, 8.8μm to 8.9μm, 8.9μm to 9μm, 9μm to 9.1μm, 9.1μm to 9.2μm, 9.2μm to 9.3μm, 9.3μm to 9.4μm, 9.4μm to 9.5μm, 9.5μm to 9.6μm, 9.6μm to 9.7μm, 9.7μm to 9.8μm, 9.8μm to 9.9μm, 9.9μm to 10μm, 10μm to 10.1μm, 10.1μm to 10.2μm, 10.2μm to 10.3μm, 10.3μm to 10.4μm, 10 .4μm to 10.5μm, 10.5μm to 10.6μm, 10.6μm to 10.7μm, 10.7μm to 10.8μm, 10.8μm to 10.9μm, 10.9μm to 11μm, 11μm to 11.1μm, 11.1μm to 11.2μm, 11.2μm to 11.3μm, 11.3μm to 11.4μm, 11.4μm to 11.5μm, 11.5μm to 11.6μm, 11.6μm to 11.7μm, 11.7μm to 11.8μm, 11.8μm to 11.9μm, or 11.9μm to 12μm.

[0007] In some examples, the battery component may further include an active material layer disposed on at least a portion of the cathode current collector. The side of the aluminum alloy facing the active material layer may be a shiny side. Alternatively, the side of the aluminum alloy facing the active material layer may be a matte side. The electrical conductivity between the active material layer and the cathode current collector may range from 0.0275 S / m to 0.0675 S / m. Optionally, the electrical conductivity between the active material layer and the cathode current collector may range from 0.04 S / m to 0.0675 S / m. Example conductivity between the first current collector and the first active material may be about 0.0275 S / m to about 0.0675 S / m, such as 0.0275 S / m to about 0.030 S / m, 0.030 S / m to 0.035 S / m, 0.035 S / m to 0.040 S / m, 0.040 S / m to 0.045 S / m, 0.045 S / m to 0.050 S / m, 0.050 S / m to 0.055 S / m, 0.055 S / m to 0.060 S / m, 0.060 S / m to 0.065 S / m, or 0.065 S / m to 0.0675 S / m.

[0008] In some examples, the cathode current collector can include a recycled content aluminum alloy. For example, the cathode current collector can include up to 50% recycled aluminum content. Example percentages of recycled aluminum content may include 0% recycled aluminum content, 1% recycled aluminum content, 2% recycled aluminum content, 3% recycled aluminum content, 4% recycled aluminum content, 5% recycled aluminum content, 6% recycled aluminum content, 7% recycled aluminum content, 8% recycled aluminum content, 9% recycled aluminum content, 10% recycled aluminum content, 11% recycled aluminum content, 12% recycled aluminum content, 13% recycled aluminum content, 14% recycled aluminum content, 15% recycled aluminum content, 16% recycled aluminum content, 17% recycled aluminum content, 18% recycled aluminum content, 19% recycled aluminum content, 20% recycled aluminum content, 21% recycled aluminum content, 22% recycled aluminum content, 23% recycled aluminum content, 24% recycled aluminum content, 25% recycled aluminum content, % recycled aluminum composition, 26% recycled aluminum composition, 27% recycled aluminum composition, 28% recycled aluminum composition, 29% recycled aluminum composition, 30% recycled aluminum composition, 31% recycled aluminum composition, 32% recycled aluminum composition, 33% recycled aluminum composition, 34% recycled aluminum composition, 35% recycled aluminum composition, 36% recycled aluminum composition, 37% recycled aluminum composition, 38% recycled aluminum composition, 39% recycled aluminum composition, 40% recycled aluminum composition, 41% recycled aluminum composition, 42% recycled aluminum composition, 43% recycled aluminum composition, 44% recycled aluminum composition, 45% recycled aluminum composition, 46% recycled aluminum composition, 47% recycled aluminum composition, 48% recycled aluminum composition, 49% recycled aluminum composition, or 50% recycled aluminum composition.

[0009] The battery component can maintain the specific capacity at more than 90% of the initial specific capacity within up to 3000 cycles. For example, the cathode current collector can help maintain the specific capacity at more than 90% of the initial specific capacity within the following cycles: up to 3000 cycles, up to 2500 cycles, up to 2000 cycles, up to 1500 cycles, up to 1000 cycles, up to 900 cycles, up to 800 cycles, up to 700 cycles, up to 600 cycles, up to 500 cycles, up to 400 cycles, up to 300 cycles, up to 200 cycles, up to 100 cycles, 200 cycles to 3000 cycles, 500 cycles to 1000 cycles, 1000 cycles to 1500 cycles, 1500 cycles to 2000 cycles, 2000 cycles to 2500 cycles or 2500 cycles to 3000 cycles.

[0010] Optionally, the battery component can maintain energy density above 90% of the initial energy density for up to 3000 cycles. For example, the cathode current collector can help maintain energy density above 90% of the initial energy density for up to 3000 cycles, up to 2500 cycles, up to 2000 cycles, up to 1500 cycles, up to 1000 cycles, up to 900 cycles, up to 800 cycles, up to 700 cycles, up to 600 cycles, up to 500 cycles, up to 400 cycles, up to 300 cycles, up to 200 cycles, up to 100 cycles, 200 cycles to 3000 cycles, 500 cycles to 1000 cycles, 1000 cycles to 1500 cycles, 1500 cycles to 2000 cycles, 2000 cycles to 2500 cycles, or 2500 cycles to 3000 cycles.

[0011] In some examples, the battery component may further include a conductive layer disposed on at least a portion of the surface of the cathode current collector. The conductive layer may be a carbonaceous material. In some examples, the 8xxx series aluminum may be an 8079 series aluminum alloy, an 8090 series aluminum alloy, or an 8077 series aluminum alloy.

[0012] In some examples, the 8xxx series aluminum alloy may include Al and at least one of Si, Cu, Fe, or Zn. For example, the 8xxx series aluminum alloy may include up to 0.3 wt % Si. Example percentages of Si in thin gauge 8xxx series aluminum alloys may include up to 0.3 wt %, up to 0.29 wt %, up to 0.28 wt %, up to 0.27 wt %, up to 0.26 wt %, up to 0.25 wt %, up to 0.24 wt %, up to 0.23 wt %, up to 0.22 wt %, up to 0.21 wt %, up to 0.20 wt %, up to 0.19 wt %, up to 0.18 wt %, up to 0.17 wt %, up to 0.16 wt %, up to 0.15 wt %, up to 0.14 wt %, up to 0.13 wt %, %, up to 0.12 wt %, up to 0.11 wt %, up to 0.10 wt %, up to 0.09 wt %, up to 0.08 wt %, up to 0.07 wt %, up to 0.06 wt %, up to 0.05 wt %, up to 0.04 wt %, up to 0.03 wt %, up to 0.02 wt %, up to 0.01 wt %, 0.05 wt % to 0.10 wt %, 0.10 wt % to 0.15 wt %, 0.15 wt % to 0.20 wt %, 0.20 wt % to 0.25 wt % or 0.25 wt % to 0.30 wt %.

[0013] 8xxx series aluminum alloys may include up to 0.05 wt % Cu. Example percentages of Cu in thin gauge 8xxx series aluminum alloys may include up to 0.05 wt %, up to 0.04 wt %, up to 0.03 wt %, up to 0.02 wt %, up to 0.01 wt %, 0.01 wt % to 0.02 wt %, 0.02 wt % to 0.03 wt %, 0.03 wt % to 0.04 wt %, or 0.04 wt % to 0.05 wt %.

[0014] 8xxx series aluminum alloys may include up to 1.3 wt % Fe. Example percentages of Fe in thin gauge 8xxx series aluminum alloys may include up to 1.3 wt %, such as up to 1.2 wt %, up to 1.1 wt %, up to 1.0 wt %, up to 0.9 wt %, up to 0.8 wt %, up to 0.7 wt %, up to 0.6 wt %, up to 0.5 wt %, up to 0.4 wt %, up to 0.3 wt %, up to 0.2 wt %, up to 0.1 wt %, 0.1 to 1.3 wt %. %, 0.2 wt % to 0.3 wt %, 0.3 wt % to 0.4 wt %, 0.4 wt % to 0.5 wt %, 0.5 wt % to 0.6 wt %, 0.6 wt % to 0.7 wt %, 0.7 wt % to 0.8 wt %, 0.8 wt % to 0.9 wt %, 0.9 wt % to 1.0 wt %, 1.0 wt % to 1.1 wt %, 1.1 wt % to 1.2 wt %, or 1.2 wt % to 1.3 wt %.

[0015] 8xxx series aluminum alloys may include up to 0.10 wt % Zn. Example percentages of Zn may include up to 0.10 wt %, up to 0.09 wt %, up to 0.08 wt %, up to 0.07 wt %, up to 0.06 wt %, up to 0.05 wt %, up to 0.04 wt %, up to 0.03 wt %, up to 0.02 wt %, up to 0.01 wt %, 0.01 wt % to 0.02 wt %, 0.02 wt % to 0.03 wt %, 0.03 wt % to 0.04 wt %, 0.04 wt % to 0.05 wt %, 0.05 wt % to 0.06 wt %, 0.06 wt % to 0.07 wt %, 0.07 wt % to 0.08 wt %, 0.08 wt % to 0.09 wt %, or 0.09 wt % to 0.10 wt %.

[0016] In some aspects, methods are described herein for methods for manufacturing battery components such as from 1xxx series aluminum alloys or 8xxx series aluminum alloys. An example method of this aspect includes providing a cathode current collector, which comprises a 1xxx series aluminum alloy or an 8xxx series aluminum alloy. The thickness of the cathode current collector can be 5μm to 12μm. The method may also include applying a cathode active material to the surface of the cathode current collector. In some examples, the method may also include subjecting the cathode current collector to a coating process to form a conductive layer. The conductive layer may be a carbonaceous material. The battery component made by the method of this aspect may include any battery component described herein.

[0017] In some aspects, the battery may include an anode and a cathode. The cathode may include any battery component described herein as a cathode current collector, and a cathode active material in contact with the cathode current collector. The battery may also include an electrolyte positioned between the cathode and the anode. The electrolyte may be a liquid electrolyte or a solid electrolyte.

[0018] In some examples, due to the rolling method used to produce the aluminum alloy current collector, each aluminum alloy current collector (e.g., corresponding to the aluminum foil layer) may have opposite surface morphology (e.g., one matte and one shiny). In some examples, the aluminum foil may be produced in pairs, such as during the rolling process, positioning the first aluminum alloy substrate adjacent to the second aluminum alloy substrate to produce a pair of foils (sometimes referred to as double rolled foils). In this configuration, the surfaces of the foils facing each other will have a dull or matte surface, while the surface of the foil contacting the rolling equipment will have a shiny or shiny surface. Double rolling can be advantageously used for the preparation of foils, for example, because such a rolling process can allow for increased production, because two foils can be produced during a single set of rolling operations. In addition, by doubling the thickness when double rolling two substrates, the roll gap can be about twice the resulting thickness of the pair of foils (e.g., a 20 μm roll gap can be used when making two 10 μm foils in contact with each other). The increased roll gap can be more efficient in operation because a larger roll gap can be easier to maintain, but this configuration can still allow for a suitably thin foil.

[0019] For some aluminum alloy current collectors, it may be desirable that both surfaces have a shiny surface configuration. In some examples, this may be for aesthetic reasons, to improve operating consistency, or to improve battery performance. In some cases, the preparation of aluminum foil such as for use as an aluminum alloy current collector may be achieved by rolling a single layer with a small roll gap, in which both the top and bottom surfaces are shiny surfaces. In this way, both the top and bottom surfaces of a single foil layer may be in contact with the rolling equipment, and result in both surfaces having a shiny morphology or appearance.

[0020] For other aluminum alloy current collectors, it may be desirable to have a matte surface morphology on both surfaces. In some examples, this may provide operational advantages or improve battery performance, such as better bonding to the active material than to the shiny side. However, forming an aluminum alloy foil having a matte morphology on both surfaces is generally not possible using a single rolling technique for preparing a foil having shiny surfaces on both surfaces, or a double rolling technique for preparing a foil having opposite morphologies (e.g., one shiny and one matte) on both surfaces of the foil. The various aspects described herein overcome this problem and allow for the preparation of an aluminum foil having a matte morphology on both surfaces.

[0021] Thus, in one aspect, a method for preparing an aluminum foil is described herein, wherein both surfaces of the foil have a matte morphology. An exemplary method of this aspect includes feeding three or more aluminum alloy sheets to a rolling mill stand to reduce the size of the three or more aluminum alloy sheets and produce three or more aluminum alloy foils. In this rolling configuration, at least one of the aluminum alloy foils may have two surfaces exhibiting a matte surface morphology. For example, an aluminum foil having both surfaces exhibiting a matte surface morphology may only contact another aluminum layer during rolling, without contacting the rolling mill stand.

[0022] In some examples, the three or more aluminum alloy sheets may include three aluminum alloy sheets. Feeding three aluminum alloy sheets to the mill stand can be used to achieve a three-fold productivity increase for rolling a single aluminum alloy sheet (single rolling). Similarly, feeding three aluminum alloy sheets to the mill stand can be used to achieve a 1.5-fold productivity increase for rolling a pair of aluminum alloy sheets (double rolling) using the same foil rolling practice. In this configuration, the center sheet of the three sheets may have two surfaces with a matte finish after rolling.

[0023] In some examples, three or more aluminum alloy sheets may include four aluminum alloy sheets. Feeding four aluminum alloy sheets to the mill stand can be used to achieve a four-fold productivity increase for rolling a single aluminum alloy sheet (single rolling). Similarly, feeding four aluminum alloy sheets to the mill stand can be used to achieve a 2-fold productivity increase for rolling a pair of aluminum alloy sheets (double rolling) using the same foil rolling practice. In this configuration, a pair of center sheets in the four sheets may have two surfaces with matte morphology after rolling.

[0024] In some examples, feeding the three or more aluminum alloy sheets to the rolling mill stand may include feeding each of the three or more sheets to the rolling mill stand individually. In other examples, at least two of the three or more aluminum alloy sheets may be fed to the rolling mill stand as a pair of coupled aluminum alloy sheets, such as having been subjected to a twin rolling or co-rolling process (e.g., where the aluminum alloy sheets are rolled together as a pair and then optionally coiled together as a pair).

[0025] Other objects and advantages will become apparent from the following detailed description given by way of non-limiting example. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] This description refers to the following drawings, in which the same reference numerals are used in different drawings to illustrate the same or similar components.

[0027] Figure 1 A schematic overview of an example method for producing a thin gauge 1xxx series or 8xxx series aluminum alloy product is provided.

[0028] Figure 2 A schematic overview of an example method for producing two thin gauge 1xxx series or 8xxx series aluminum alloy products is provided, wherein both products include one surface having a shiny finish and one surface having a matte finish.

[0029] Figure 3 A schematic overview of an example method for manufacturing three thin gauge 1xxx series or 8xxx series aluminum alloy products is provided, wherein two of the products include one surface having a shiny finish and one surface having a matte finish, and one product includes two surfaces having a matte finish.

[0030] Figure 4 A schematic overview of an example method for manufacturing four thin gauge 1xxx series or 8xxx series aluminum alloy products is provided, wherein two products include one surface having a shiny finish and one surface having a matte finish, and two products include two surfaces having a matte finish.

[0031] Figure 5 is a schematic diagram of an example lithium-ion battery cell including a thin-gauge aluminum alloy cathode current collector.

[0032] Figure 6 is a schematic diagram of an example pull-out test for a thin-gauge aluminum alloy cathode current collector.

[0033] Figure 7 is a diagram of an example testing procedure for a battery cell including a thin gauge aluminum alloy cathode current collector.

[0034] Figure 8 is a graph depicting the bond strengths obtained from pull-off tests on example thin gauge aluminum alloy cathode current collectors.

[0035] Fig. 9 is a graph depicting the resulting specific conductivity of an example thin gauge aluminum alloy cathode current collector.

[0036] Fig.10is a graph depicting the specific discharge capacity resulting from cycle testing of an example battery cell including a thin gauge aluminum alloy cathode current collector.

[0037] Fig.11 is a graph depicting the resulting specific discharge capacity during C-rate testing of example battery cells including a thin gauge aluminum alloy cathode current collector.

[0038] Fig.12 is a graph depicting the resulting energy density levels at the cathode level during cycle testing of an example battery cell including a thin gauge aluminum alloy cathode current collector.

[0039] Fig.13 is a graph depicting the resulting energy density levels at the cathode level during C-rate testing conducted on an example battery cell including a thin gauge aluminum alloy cathode current collector. DETAILED DESCRIPTION

[0040] Battery components, such as cathode current collectors, including thin gauge 1xxx series aluminum alloys or 8xxx series aluminum alloys are described herein. The thickness of the cathode current collector may be between 5 μm and 12 μm. Conventional cathode current collectors are typically made of 1xxx series aluminum alloys (such as 1085 series aluminum alloys) with a thickness between 12 μm and 50 μm. In some cases, the cycle life of a battery cell including a conventional cathode current collector may be about 200 hours. In contrast, the cycle life of a battery cell including a cathode current collector made of a thin gauge 1xxx series aluminum alloy or 8xxx series aluminum alloy as described herein may be significantly longer than a conventional cathode current collector tested and manufactured under similar conditions. In some examples, the cycle life of a battery cell including such a cathode current collector may be between 600 and 800 hours or longer. In some examples, the specific capacity of the cathode incorporating such a current collector can be maintained at more than 90% of the original specific capacity during a cycle life, such as up to 250 cycles, 300 cycles, 350 cycles, 400 cycles, 450 cycles, 500 cycles, 750 cycles, 1000 cycles, 1500 cycles, 2000 cycles, 3000 cycles or more cycles. In addition, the energy density of the cathode incorporating such a current collector can be maintained at more than 90% of the original energy density during a cycle life, such as up to 250 cycles, 300 cycles, 350 cycles, 400 cycles, 450 cycles, 500 cycles, 750 cycles, 1000 cycles, 1500 cycles, 2000 cycles, 3000 cycles or more cycles.

[0041] In some examples, the increased iron content of the 8xxx series aluminum alloys compared to the 1xxx series aluminum alloys can allow for a stronger and therefore thinner gauge. As described herein, the reduced mass of the 8xxx series aluminum alloys in thin gauge can provide increased energy density and specific capacity for cathodes incorporating thin gauge 8xxx series aluminum alloy current collectors. Other metals included in the 8xxx series aluminum alloys, such as Si, Cu, Fe, and Zn, can optionally contribute to the increased energy density and specific capacity of the cathode.

[0042] In some examples, manufacturing a thin gauge 1xxx series aluminum alloy or 8xxx series aluminum alloy can produce a flash side and a matte side. The energy density, specific capacity, active material adhesion, etc. of a lithium-ion battery can be influenced, controlled, or customized based on the side of the aluminum alloy current collector facing the active material layer in the lithium-ion battery. For example, orienting the matte side to face the active material layer can result in increased energy density, specific capacity, and active material adhesion of the lithium battery compared to placing the flash side to face the active material layer. When the active material layer faces the matte side, the matte side can also have increased conductivity or lower interfacial resistance for the active material layer compared to the flash side.

[0043] Definition and Description:

[0044] As used herein, the terms "invention," "the invention," "this invention," and "present invention" are intended to broadly refer to all subject matter of this patent application and the appended claims. Statements containing these terms should not be construed as limiting the subject matter described herein, or limiting the meaning or scope of the following patent claims.

[0045] In this specification, reference is made to alloys identified by AA numbers and other related designations such as "Series" or "7xxx". To understand the number designation system most commonly used to name and identify aluminum and its alloys, see "International Alloy Designations and Chemical Composition Limits for Wrought Aluminum and Wrought Aluminum Alloys" or "Registration Record of Aluminum Association Alloy Designations and Chemical Compositions Limits for Aluminum Alloys in the Form of Castings and Ingot", both published by the Aluminum Association.

[0046] As used herein, the thickness of a plate is generally greater than about 15 mm. For example, a plate may refer to an aluminum product having a thickness greater than about 15 mm, greater than about 20 mm, greater than about 25 mm, greater than about 30 mm, greater than about 35 mm, greater than about 40 mm, greater than about 45 mm, greater than about 50 mm, or greater than about 100 mm.

[0047] As used herein, the thickness of the Saudi board (also referred to as a thin plate type board) is generally about 4 mm to about 15 mm. For example, the thickness of the Saudi board can be about 4 mm, about 5 mm, about 6 mm, about 7 mm, about 8 mm, about 9 mm, about 10 mm, about 11 mm, about 12 mm, about 13 mm, about 14 mm or about 15 mm.

[0048] As used herein, thin plate generally refers to an aluminum product having a thickness of less than about 4 mm. For example, the thickness of the thin plate may be less than about 4 mm, less than about 3 mm, less than about 2 mm, less than about 1 mm, less than about 0.5 mm, or less than about 0.3 mm (e.g., about 0.2 mm).

[0049] As used herein, foil generally refers to an aluminum product having a thickness of less than about 0.20 mm. For example, the thickness of the foil may be less than about 0.20 mm, less than about 0.15 mm, less than about 0.10 mm, less than about 0.075 mm, less than about 0.05 mm, or less than about 0.025 mm. In some examples, the thickness of the foil is less than or about 0.010 mm, 0.009 mm, 0.008 mm, 0.007 mm, 0.006 mm, or 0.005 mm.

[0050] Reference may be made to alloy tempers or conditions in this application. To understand the most commonly used alloy temper descriptions, please refer to "American National Standards (ANSI) H35 on Alloy and Temper Designation Systems". F temper or condition refers to a manufactured aluminum alloy. O temper or condition refers to an aluminum alloy after annealing. Hxx temper or condition (also referred to herein as H temper) refers to a non-heat-treatable aluminum alloy that has been subjected to or not subjected to heat treatment (e.g., annealing) after cold rolling. Suitable H tempers include HX1, HX2, HX3, HX4, HX5, HX6, HX7, HX8 or HX9 tempers. T1 temper or condition refers to an aluminum alloy that has been cooled from hot working and subjected to natural aging treatment (e.g., at room temperature). T2 temper or condition refers to an aluminum alloy that has been cooled from hot working, cold worked, and subjected to natural aging treatment. T3 temper or condition refers to an aluminum alloy that has been solution heat treated, cold worked, and naturally aged. T4 temper or condition refers to an aluminum alloy that has been solution heat treated and naturally aged. The T5 condition or state refers to aluminum alloys that have been cooled from hot working and artificially aged (at elevated temperatures). The T6 condition or state refers to aluminum alloys that have been solution heat treated and artificially aged. The T7 condition or state refers to aluminum alloys that have been solution heat treated and artificially aged. The T8x condition or state refers to aluminum alloys that have been solution heat treated, cold worked, and artificially aged. The T9 condition or state refers to aluminum alloys that have been solution heat treated, artificially aged, and cold worked. The W condition or state refers to aluminum alloys that have been solution heat treated.

[0051] As used herein, terms such as "cast metal product", "cast product", "cast aluminum alloy product" and the like are interchangeable and refer to products produced by direct chill casting (including direct chill co-casting) or semi-continuous casting, continuous casting (including, for example, by using a twin-belt caster, a twin-roll caster, a block caster or any other continuous casting machine), electromagnetic casting, hot top casting or any other casting method.

[0052] As used herein, "room temperature" may include a temperature of about 15° C. to about 30° C., such as about 15° C., about 16° C., about 17° C., about 18° C., about 19° C., about 20° C., about 21° C., about 22° C., about 23° C., about 24° C., about 25° C., about 26° C., about 27° C., about 28° C., about 29° C., or about 30° C. As used herein, "ambient conditions" may include a temperature of approximately room temperature, a relative humidity of about 20% to about 100%, and an atmospheric pressure of about 975 millibars (mbar) to about 1050 mbar. For example, the relative humidity can be about 20%, about 21%, about 22%, about 23%, about 24%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47%, about 48%, about 49%, about 50%, about 51%, about 52%, about 53%, about 54%, about 55%, about 56%, about 57%, about 58%, about 59%, about 60%, about 61%, about 62%, about 63%, about 64%, about 65%, about 66%, about 67%, about 68%, about 69%, about 70%, about 71%, about 72%, about 73%, about 74%, about 75%, about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99%, about 100%, about 101%, about 102%, about 103%, about 104%, about 105%, about 106%, about 107%, about 108%, about 109%, about 110%, about 111%, about 112%, about 113%, about 114%, about 115%, about 116%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99%, about 100%, about 100%, about 101%, about 102%, about 103%, about 104%, about 105%, about 106%, about 107%, about 108%, about 109%, about 110%, about 111%, about 112%, about 113%, about 114%, about 115%, about 116%, about 117%, about 118%, about 119%, about 120%, about 121%, about 122%, about 123%, about 124%, about 125%, about 126%, about 127%, about 128%, about 129%, about 130%, about 131%, about 132%, about 133%, about 134%, about 135%, about 136%, about 137%, about 138%, about 139%, about 140%, about 141%, about 142%, about 143%, about 144%, about 145%, about 146%, about 147%, about 148%, about 149%, about 150%, about For example, the atmospheric pressure may be about 975 mbar, about 980 mbar, about 985 mbar, about 990 mbar, about 995 mbar, about 1000 mbar, about 1005 mbar, about 1010 mbar, about 1015 mbar, about 1020 mbar, about 1025 mbar, about 1030 mbar, about 1035 mbar, about 1040 mbar, about 1045 mbar, about 1050 mbar, or any value therebetween.

[0053] All ranges disclosed herein should be understood to encompass any and all subranges included therein. For example, a specified range of "1 to 10" should be considered to include any and all subranges between a minimum of 1 and a maximum of 10 (and including 1 and 10); that is, all subranges start with a minimum of 1 or greater (e.g., 1 to 6.1) and end with a maximum of 10 or less (e.g., 5.5 to 10). Unless otherwise stated, when referring to the composition amount of an element, the expression "up to" means that the element is optional and includes zero percent composition of the particular element. Unless otherwise stated, all composition percentages are weight percent (wt%).

[0054] As used herein, "a," "an," and "the" include both singular and plural references unless the context clearly indicates otherwise.

[0055] In the following examples, aluminum alloy products and parts thereof may be described in terms of their elemental composition in weight percent (wt%). In each alloy, the remainder is aluminum, with a maximum wt% of 0.15% for the sum of all impurities.

[0056] Incidental elements, such as grain refiners and deoxidizers, or other additives may be present in the present invention and may themselves add other properties without departing from or significantly altering the alloys described herein or the properties of the alloys described herein.

[0057] Small amounts of unavoidable impurities, including materials or elements, may be present in the alloy due to the inherent properties of aluminum or leaching from contact with processing equipment. As described, some alloys may contain no more than about 0.25% by weight of any element other than alloying elements, incidental elements, and unavoidable impurities.

[0058] The terms "surface morphology" and "surface finish" are used herein to refer to the properties of the surface of a metal product, such as a rolled aluminum alloy product (e.g., aluminum alloy sheet or aluminum alloy foil). The surface finish may be characterized based on its appearance and may provide a qualitative or quantitative measure of how well a surface reflects light in a specular direction. Qualitative measures of surface finish may include matte finish or matte morphology on the one hand, and gloss finish, gloss morphology, shimmer finish, shimmer morphology, shiny morphology, or shiny finish on the other hand. For a matte finish or matte morphology surface finish, the specular gloss may be lower than the specular gloss of other surface finishes, such as gloss finish, gloss morphology, shimmer finish, shimmer morphology, shiny morphology, or shiny finish. Thus, the finish morphology may be relative. A quantitative measure of surface finish may be determined using one or more standards, such as for measuring specular gloss. Example standards related to the measurement of gloss include, but are not limited to, ISO 2813, ISO 7668, ISO 7759, ASTM D523, ASTM D4039, ASTM C346, ASTM D457, ASTM D7163, JIS Z 8741, DIN 67530. In some examples, a matte finish surface exhibits a low gloss level, such as a gloss level of about 30% or less. In some examples, a glitter, gloss, or shiny finish surface exhibits a medium or high gloss level, such as a gloss level of about 30% or more. Example gloss levels for matte finish surfaces may be less than or about 30%, less than or about 25%, less than or about 20%, less than or about 15%, less than or about 10%, or less than or about 5%. Example gloss levels for a shimmer, glossy, or shiny surface finish may be greater than or about 40%, greater than or about 45%, greater than or about 50%, greater than or about 55%, greater than or about 60%, greater than or about 65%, greater than or about 70%, greater than or about 75%, or greater than or about 80%. In some examples, the surface roughness of the shimmer, glossy, or shiny finish surface may be about 0.01 μm to about 0.15 μm. In some examples, the surface roughness of the matte finish surface may be about 0.15 μm to about 0.5 μm. Example surface roughness of a shiny, glossy or bright finish surface may be 0.01 μm to 0.02 μm, 0.02 μm to 0.03 μm, 0.03 μm to 0.04 μm, 0.04 μm to 0.05 μm, 0.05 μm to 0.06 μm, 0.06 μm to 0.07 μm, 0.07 μm to 0.08 μm, 0.08 μm to 0.09 μm, 0.09 μm to 0.10 μm, 0.10 μm to 0.11 μm, 0.11 μm to 0.12 μm, 0.12 μm to 0.13 μm, 0.13 μm to 0.14 μm, or 0.14 μm to 0.15 μm.Example surface roughness of a matte finish surface may be 0.15 μm to 0.16 μm, 0.16 μm to 0.17 μm, 0.17 μm to 0.18 μm, 0.18 μm to 0.19 μm, 0.19 μm to 0.20 μm, 0.20 μm to 0.21 μm, 0.21 μm to 0.22 μm, 0.22 μm to 0.23 μm, 0.24 μm to 0.26 μm, 0.27 μm to 0.28 μm, 0.29 μm to 0.30 μm, 0.31 μm to 0.32 μm, 0.33 μm to 0.36 μm, 0.37 μm to 0.38 μm, 0.39 μm to 0.40 μm, 0. μm, 0.23 μm to 0.24 μm or 0.24 μm to 0.25 μm, 0.25 μm to 0.26 μm, 0.26 μm to 0.27 μm, 0.27 μm to 0.28 μm, 0.28 μm to 0.29 μm, 0.29 μm to 0.30 μm, 0.30 μm to 0.31 μm, 0.31 μm to 0.32 μm m, 0.32 μm to 0.33 μm, 0.33 μm to 0.34 μm or 0.34 μm to 0.35 μm, 0.35 μm to 0.36 μm, 0.36 μm to 0.37 μm, 0.37 μm to 0.38 μm, 0.38 μm to 0.39 μm, 0.39 μm to 0.40 μm, 0.40 μm to 0.41 μm , 0.41μm to 0.42μm, 0.42μm to 0.43μm, 0.43μm to 0.44μm or 0.44μm to 0.45μm, 0.45μm to 0.46μm, 0.46μm to 0.47μm, 0.47μm to 0.48μm, 0.48μm to 0.49μm, or 0.19μm to 0.20μm.

[0059] Methods for producing alloys and aluminum alloy products

[0060] Figure 1 A schematic overview of an example method for manufacturing a thin gauge 1xxx series aluminum alloy product or an 8xxx series aluminum alloy product is provided. Figure 1 The method may begin at step 105, where an aluminum alloy 106 may be cast to produce a cast aluminum alloy product 107, such as an ingot or other cast product. At step 110, the cast aluminum alloy product 107 may be homogenized to form a homogenized aluminum alloy product 111. At step 115, the homogenized aluminum alloy product 111 may be subjected to one or more hot rolling passes and / or one or more cold rolling passes to form a rolled aluminum alloy product 112, which may correspond to an aluminum alloy article, such as an aluminum alloy plate, an aluminum alloy slat, or an aluminum alloy sheet. Optionally, the rolled aluminum alloy product 112 may be subjected to one or more forming or stamping processes to form an aluminum alloy article.

[0061] The thin gauge 1xxx series aluminum alloy and 8xxx series aluminum alloy described herein can be cast using any suitable casting method known to those of ordinary skill in the art. As several non-limiting examples, the casting process may include direct chilling (DC) casting process or continuous casting (CC) process. The continuous casting system may include a pair of moving relative casting surfaces (e.g., moving relative belts, rollers or blocks), a casting cavity and a molten metal injector positioned between the relative casting surfaces of the pair of movements. The molten metal injector may have an end opening, from which the molten metal may leave the molten metal injector and be injected into the casting cavity.

[0062] The cast ingot, cast slab or other cast product may be processed by any suitable means. Such processing steps include, but are not limited to, homogenization, hot rolling, cold rolling, solution heat treatment and optional pre-aging steps.

[0063] In the homogenization step, the cast product is heated to a temperature ranging from about 400°C to about 560°C. For example, the cast product may be heated to a temperature of about 400°C, about 410°C, about 420°C, about 430°C, about 440°C, about 450°C, about 460°C, about 470°C, about 480°C, about 490°C, about 490°C, about 500°C, about 510°C, about 520°C, about 520°C, about 540°C, about 550°C, or about 560°C. In some examples, homogenization is performed at a temperature within 50°C of the solidus temperature of the cast product or its alloy. The product is then allowed to soak (i.e., maintained at the indicated temperature) for a period of time to form a homogenized product. In some examples, the total time for the homogenization step (including the heating stage and the soaking stage) may be up to 24 hours. For example, for the homogenization step, the product may be heated to up to 500°C and soaked for a total time of up to 18 hours. Optionally, for the homogenization step, the product may be heated to less than 490°C and homogenized for a total time greater than 18 hours. In some cases, the homogenization step includes multiple processes. In some non-limiting examples, the homogenization step includes heating the cast product to a first temperature for a first period of time, and then heating to a second temperature for a second period of time. For example, the cast product may be heated to about 465°C for about 3.5 hours, and then heated to about 480°C for about 6 hours.

[0064] After the homogenization step, a hot rolling step may be performed. Before starting the hot rolling, the homogenized product may be allowed to cool to a temperature between 300° C. and 450° C. For example, the homogenized product may be allowed to cool to a temperature between 325° C. and 425° C. or from 350° C. to 400° C. The homogenized product may then be hot rolled at a temperature between 300°C and 450°C to form a hot rolled plate, hot rolled satur plate or hot rolled sheet having a specification between 3 mm and 200 mm (e.g., 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 15 mm, 20 mm, 25 mm, 30 mm, 35 mm, 40 mm, 45 mm, 50 mm, 55 mm, 60 mm, 65 mm, 70 mm, 75 mm, 80 mm, 85 mm, 90 mm, 95 mm, 100 mm, 110 mm, 120 mm, 130 mm, 140 mm, 150 mm, 160 mm, 170 mm, 180 mm, 190 mm, 200 mm or any value therebetween).

[0065] Optionally, the cast product may be a continuously cast product that may be allowed to cool to a temperature between 300° C. and 450° C. For example, the continuously cast product may be allowed to cool to a temperature between 325° C. and 425° C. or from 350° C. to 400° C. The continuously cast product may then be hot rolled at a temperature between 300° C. and 450° C. to form a hot rolled plate, hot rolled satur plate or hot rolled sheet having a specification between 3 mm and 200 mm (e.g., 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 15 mm, 20 mm, 25 mm, 30 mm, 35 mm, 40 mm, 45 mm, 50 mm, 55 mm, 60 mm, 65 mm, 70 mm, 75 mm, 80 mm, 85 mm, 90 mm, 95 mm, 100 mm, 110 mm, 120 mm, 130 mm, 140 mm, 150 mm, 160 mm, 170 mm, 180 mm, 190 mm, 200 mm or any value therebetween). During hot rolling, temperature and other operating parameters may be controlled so that the temperature of the hot rolled intermediate product exiting the hot rolling mill does not exceed about 470°C, about 450°C, about 440°C, or about 430°C.

[0066] Cold rolling mills can be used to cold roll cast, homogenized or hot rolled products into thinner products, such as cold rolled sheets. The cold rolled product can have a specification between about 0.5 mm and 10 mm (e.g., between about 0.7 mm and 6.5 mm). Optionally, the cold rolled product can have the following specifications: 0.5 mm, 1.0 mm, 1.5 mm, 2.0 mm, 2.5 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm, 5.0 mm, 5.5 mm, 6.0 mm, 6.5 mm, 7.0 mm, 7.5 mm, 8.0 mm, 8.5 mm, 9.0 mm, 9.5 mm or 10.0 mm. Cold rolling may be performed to obtain a final gauge thickness that represents a gauge reduction of up to 85% (e.g., a reduction of up to 10%, up to 20%, up to 30%, up to 40%, up to 50%, up to 60%, up to 70%, up to 80%, or up to 85%) compared to the gauge before cold rolling began. Optionally, an intermediate annealing step may be performed during the cold rolling step, such as applying a first cold rolling process, followed by an annealing process (intermediate annealing), and then a second cold rolling process. The intermediate annealing step may be performed at a temperature of about 300°C to about 450°C (e.g., about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, about 400°C, about 410°C, about 420°C, about 430°C, about 440°C, or about 450°C). In some cases, the intermediate annealing step includes multiple processes. In some non-limiting examples, the intermediate annealing step includes heating the partially cold rolled product to a first temperature for a first period of time and then heating to a second temperature for a second period of time. For example, the partially cold rolled product may be heated to about 410° C. for about 1 hour and then heated to about 330° C. for about 2 hours.

[0067] Subsequently, the cast, homogenized or rolled product may undergo a solution heat treatment step. The solution heat treatment step may be any treatment suitable for thin plates that results in solubilization of soluble particles. The cast, homogenized or rolled product may be heated to a peak metal temperature (PMT) of up to 590°C (e.g., 400°C to 590°C), and soaked for a period of time at the PMT to form a hot product. For example, the cast, homogenized or rolled product may be soaked at 480°C for up to 30 minutes (e.g., 0 seconds, 60 seconds, 75 seconds, 90 seconds, 5 minutes, 10 minutes, 20 minutes, 25 minutes or 30 minutes) of soaking time. After heating and soaking, the hot product is rapidly cooled to a temperature between 500°C and 200°C at a rate greater than 200°C / second to form a heat-treated product. In one example, the hot product is cooled to a temperature between 450°C and 200°C at a quenching rate greater than 200°C / second. Optionally, in other cases, the cooling rate may be faster.

[0068] After quenching, the heat treated product may optionally be pre-aged by reheating before coiling. The pre-aging treatment may be performed at a temperature of about 70°C to about 125°C for a period of up to 6 hours. For example, the pre-aging treatment may be performed at a temperature of about 70°C, about 75°C, about 80°C, about 85°C, about 90°C, about 95°C, about 100°C, about 105°C, about 110°C, about 115°C, about 120°C, or about 125°C. Optionally, the pre-aging treatment may be performed for about 30 minutes, about 1 hour, about 2 hours, about 3 hours, about 4 hours, about 5 hours, or about 6 hours. The pre-aging treatment may be performed by passing the heat treated product through a heating device, such as a device that emits radiant heat, convection heat, induction heat, infrared heat, etc.

[0069] Cast products described herein can be used to manufacture products or other suitable products in the form of thin plates, plates. For example, the plate comprising products as described herein can be prepared in the following manner: in a homogenization step, ingots are processed or cast products are cast in a continuous casting machine, followed by a hot rolling step. In the hot rolling step, the cast products can be hot rolled to a specification of 200 mm thick or less (for example, about 10 mm to about 200 mm). For example, the cast products can be hot rolled into a plate with the following final specification thickness: about 10 mm to about 175 mm, about 15 mm to about 150 mm, about 20 mm to about 125 mm, about 25 mm to about 100 mm, about 30 mm to about 75 mm, or about 35 mm to about 50 mm. In some cases, the plate can be rolled into a thinner metal product, such as a thin plate.

[0070] A variety of rolling processes can be used to produce rolled products from cast products. Figure 1 As indicated, hot rolling or cold rolling may be used. In some examples, the rolled product may be subjected to multiple cold rolling processes, such as to further reduce the thickness or gauge of the rolled product to a desired value. Optionally, multiple rolled products may be rolled together simultaneously, such as in a co-rolling process, where multiple rolled products are fed to a rolling mill stand and subjected to a rolling process to reduce the gauge or thickness of each of the multiple rolled products.

[0071] Figure 2 An example of two rolled products 212 and 213 undergoing a co-rolling process is provided. Figure 2 As depicted, rolled products 212 and 213 are fed to a rolling mill stand 220 to produce a co-rolled product 215. Here, the co-rolled rolled product 215 includes two rolled products, such as Figure 2 Depending on the thickness and alloy of rolled products 212 and 213, the two rolled products of co-rolled product 215 may have the same or different thicknesses and may include the same or different aluminum alloys. Figure 2Co-rolling of the depicted process may be used to produce aluminum alloy foil, and the co-rolling process may provide double the rolling volume while using a larger gap between the rolls of the rolling mill stand 220 compared to rolling a single rolled product.

[0072] In the enlarged illustration, the surfaces of the individual rolled products of the co-rolled product 215 are identified. For the top rolled product, surfaces 231 and 232 are indicated. For the bottom rolled product, surfaces 233 and 234 are indicated. Figure 2 The depicted scheme is co-rolled, and surfaces 231 and 234 correspond to surfaces of the individual rolled products of the co-rolled product 215 that are in contact with the rolls of the rolling mill stand 220, and these surfaces may exhibit relatively shiny or shiny surfaces. In contrast, surfaces 232 and 233 correspond to surfaces of the individual rolled products of the co-rolled product 215 that are in contact only with each other, and these surfaces may exhibit matte surface finishes. Thus, each of the individual rolled products of the co-rolled product 215 may include one surface having a shiny finish and one surface having a matte finish.

[0073] Figure 3 An example is provided in which three rolled products 312, 313 and 314 are subjected to a co-rolling process. Figure 3 As depicted, rolled products 312, 313, and 314 are fed to a rolling mill stand 320 to produce a co-rolled product 315. Here, the co-rolled rolled product 315 includes three rolled products, such as Figure 3 Depending on the thickness and alloy of rolled products 312, 313, and 314, the three rolled products of co-rolled product 315 may have the same or different thicknesses and may include the same or different aluminum alloys. Figure 3 Co-rolling of the depicted process may be used to produce aluminum alloy foil, and the co-rolling process may provide three times the rolling volume while using a larger gap between the rolls of the rolling mill stand 320 compared to rolling a single rolled product.

[0074] In the enlarged illustration, the surfaces of the individual rolled products of the co-rolled product 315 are identified. For the top rolled product, surfaces 331 and 332 are indicated. For the middle rolled product, surfaces 333 and 334 are indicated. For the bottom rolled product, surfaces 335 and 336 are indicated. Figure 3The depicted scheme is co-rolled, and surfaces 331 and 336 correspond to surfaces of each rolled product of the co-rolled product 315 that are in contact with the rollers of the rolling mill stand 320, and these surfaces may exhibit relatively shiny or shiny surfaces. In contrast, surfaces 332, 333, 334, and 335 correspond to surfaces of each rolled product of the co-rolled product 315 that are in contact with only another aluminum alloy product surface rather than the roller surface, and these surfaces may exhibit a matte surface finish. Therefore, the top rolled product and the bottom rolled product of the co-rolled product 315 may each include one surface (331 and 336) with a shiny finish and one surface (332 and 335) with a matte finish, while the middle rolled product of the co-rolled product 315 may include two surfaces (333 and 334) with a matte finish.

[0075] Figure 4 An example is provided in which two co-rolled products 415 and 416 are subjected to a co-rolling process, which may be a second co-rolling process. Figure 4 As depicted, co-rolled products 415 and 416 each include two separate rolled products, such as Figure 4 The co-rolled products 415 and 416 are fed to the rolling mill stand 420 to produce the co-rolled product 425. Here, the co-rolled rolled product 425 includes four rolled products, such as Figure 4 The enlarged inset on the right is shown. Depending on the thickness and alloy of co-rolled products 415 and 416, the four rolled products of co-rolled product 415 may have the same or different thicknesses and may include the same or different aluminum alloys.

[0076] according to Figure 4 The co-rolling of the depicted process can be used to produce aluminum alloy foil, and the co-rolling process can provide four times the rolling volume compared to rolling a single rolled product while using a larger gap between the rolls of the rolling mill stand 420. In addition, Figure 4 The rolling configuration shown can be used with Figure 2 The rolling configuration depicted is the same or substantially the same except that rolled products 212 and 213 are replaced with co-rolled products 415 and 416. This configuration may be advantageous in that, for example, it is suitable for incorporating a third rolled product on the left side. Figure 3 When compared with the rolling configuration of the previous embodiment, it may not be necessary to change the rolling configuration.

[0077] exist Figure 4 In the enlarged inset on the right, the surfaces of the individual rolled products of the co-rolled product 415 are identified. For the top rolled product, surfaces 431 and 432 are indicated. For the upper intermediate rolled product, surfaces 433 and 434 are indicated. For the lower intermediate rolled product, surfaces 435 and 436 are indicated. For the bottom rolled product, surfaces 437 and 438 are indicated. Figure 4 The depicted scheme is co-rolled, and surfaces 431 and 338 correspond to surfaces of each rolled product of the co-rolled product 415 that are in contact with the rollers of the rolling mill stand 420, and these surfaces may exhibit relatively shiny or shiny surfaces. In contrast, surfaces 432, 433, 434, 435, 436, and 437 correspond to surfaces of each rolled product of the co-rolled product 415 that are in contact with only another aluminum alloy product surface rather than the roller surface, and these surfaces may exhibit a matte surface finish. Therefore, the top rolled product and the bottom rolled product of the co-rolled product 415 may each include one surface (431 and 438) with a shiny finish and one surface (432 and 437) with a matte finish, while the upper intermediate rolled product and the lower intermediate rolled product of the co-rolled product 415 may include two surfaces (433, 434, 435, and 436) with a matte finish.

[0078] Methods of using metals and metal alloys

[0079] Methods of using metals and metal alloys, including, among others, aluminum, aluminum alloys, magnesium, magnesium alloys, magnesium composites, and steel, and the resulting treated metals and metal alloys are described herein. In some examples, the metal used in the methods described herein includes an aluminum alloy, such as a 1xxx series aluminum alloy, a 2xxx series aluminum alloy, a 3xxx series aluminum alloy, a 4xxx series aluminum alloy, a 5xxx series aluminum alloy, a 6xxx series aluminum alloy, a 7xxx series aluminum alloy, or an 8xxx series aluminum alloy. Optionally, an 8xxx series alloy that can be used in the thin gauge aluminum alloy products described herein may include recycled components that may contain one or more of the following: a 1xxx series aluminum alloy, a 2xxx series aluminum alloy, a 3xxx series aluminum alloy, a 4xxx series aluminum alloy, a 5xxx series aluminum alloy, a 6xxx series aluminum alloy, a 7xxx series aluminum alloy, or an 8xxx series aluminum alloy. In some examples, materials for use in the methods described herein include non-ferrous materials, including aluminum, aluminum alloys, magnesium, magnesium-based materials, magnesium alloys, magnesium composites, titanium, titanium-based materials, titanium alloys, copper, copper-based materials, composites, sheets used in composites, or any other suitable metal, non-metal, or combination of materials. Monolithic materials as well as non-monolithic materials (such as rolled bonded materials, clad alloys, claddings, composites such as but not limited to materials containing carbon fibers) or various other materials may also be used with the methods described herein. In some examples, aluminum alloys containing iron may be used with the methods described herein.

[0080] As non-limiting examples, exemplary 1xxx series aluminum alloys for use in the methods described herein may include AA1100, AA1100A, AA1200, AA1200A, AA1300, AA1110, AA1120, AA1230, AA1230A, AA1235, AA1435, AA1145, AA1345, AA1445, AA1150, AA1350, AA1350A, AA1450, AA1370, AA1275, AA1185, AA1285, AA1385, AA1188, AA1190, AA1290, AA1193, AA1198, or AA1199.

[0081] Non-limiting exemplary 2xxx series aluminum alloys for use in the methods described herein may include AA2001, AA2002, AA2004, AA2005, AA2006, AA2007, AA2007A, AA2007B, AA2008, AA2009, AA2010, AA2011, AA2011A, AA2111, AA2111A, AA2111B, AA2012, AA2013, AA2014, AA2015, AA2016, AA2017, AA2018, AA2019, AA2020, AA2021 A2014A, AA2214, AA2015, AA2016, AA2017, AA2017A, AA2117, AA2018, AA2218, AA2618, AA2618A, AA2219, AA2319, AA2419, AA2519, AA2021, AA2022, AA2023, AA2024, AA2024A, AA2124, AA2224, AA2224A, AA2324, A A2424, AA2524, AA2624, AA2724, AA2824, AA2025, AA2026, AA2027, AA2028, AA2028A, AA2028B, AA2028C, AA2029, AA2030, AA2031, AA2032, AA2034, AA2036, AA2037, AA2038, AA2039, AA2139, AA2040, AA2041, AA 2044, AA2045, AA2050, AA2055, AA2056, AA2060, AA2065, AA2070, AA2076, AA2090, AA2091, AA2094, AA20 95, AA2195, AA2295, AA2196, AA2296, AA2097, AA2197, AA2297, AA2397, AA2098, AA2198, AA2099 or AA2199.

[0082] Non-limiting exemplary 3xxx series aluminum alloys for use in the methods described herein may include AA3002, AA3102, AA3003, AA3103, AA3103A, AA3103B, AA3203, AA3403, AA3004, AA3004A, AA3104, AA3204, AA3304, AA3005, AA3005A, AA3105, AA3105A, AA3105B, AA3203, AA3403, AA3004, AA3004A, AA3104, AA3204, AA3304, AA3005 AA3007, AA3107, AA3207, AA3207A, AA3307, AA3009, AA3010, AA3110, AA3011, AA3012, AA3012A, AA3013, AA3014, AA3015, AA3016, AA3017, AA3019, AA3020, AA3021, AA3025, AA3026, AA3030, AA3130, or AA3065.

[0083] Non-limiting exemplary 4xxx series aluminum alloys for use in the methods described herein may include AA4045, AA4004, AA4104, AA4006, AA4007, AA4008, AA4009, AA4010, AA4013, AA4014, AA4015, AA4015A, AA4115, AA4016, AA4017, AA4018, AA4019, AA4020, AA4021, AA4026, AA4032, AA4043, AA4043A, AA4143, AA4343, AA4643, AA4943, AA4044, AA4145, AA4145A, AA4046, AA4047, AA4047A, or AA4147.

[0084] Non-limiting exemplary 5xxx series aluminum alloys for use in the methods described herein may include AA5182, AA5183, AA5005, AA5005A, AA5205, AA5305, AA5505, AA5605, AA5006, AA5106, AA5010, AA5110, AA5110A, AA5210, AA5310, AA5016, AA5017, AA5018, AA5018A, AA5019, AA5019A, AA5119 ... A5119A, AA5021, AA5022, AA5023, AA5024, AA5026, AA5027, AA5028, AA5040, AA5140, AA5041, AA5042, AA5043, AA504 9. AA5149, AA5249, AA5349, AA5449, AA5449A, AA5050, AA5050A, AA5050C, AA5150, AA5051, AA5051A, AA5151, AA5251, AA5251A, AA5351, AA5451, AA5052, AA5252, AA5352, AA5154, AA5154A, AA5154B, AA5154C, AA5254, AA5354, AA5454, A A5554, AA5654, AA5654A, AA5754, AA5854, AA5954, AA5056, AA5356, AA5356A, AA5456, AA5456A, AA5456B, AA5556, AA5 556A, AA5556B, AA5556C, AA5257, AA5457, AA5557, AA5657, AA5058, AA5059, AA5070, AA5180, AA5180A, AA5082, AA51 82. AA5083, AA5183, AA5183A, AA5283, AA5283A, AA5283B, AA5383, AA5483, AA5086, AA5186, AA5087, AA5187 or AA5088.

[0085] Non-limiting exemplary 6xxx series aluminum alloys for use in the methods described herein may include AA6101, AA6101A, AA6101B, AA6201, AA6201A, AA6401, AA6501, AA6002, AA6003, AA6103, AA6005, AA6005A, AA6005B, AA6005C, AA6105, AA6205, AA6305, AA6006, AA6106, AA6206, AA6306 ... A6008, AA6009, AA6010, AA6110, AA6110A, AA6011, AA6111, AA6012, AA6012A, AA6013, AA6113, AA6014, AA6015, AA 6016, AA6016A, AA6116, AA6018, AA6019, AA6020, AA6021, AA6022, AA6023, AA6024, AA6025, AA6026, AA6027, AA60 28. AA6031, AA6032, AA6033, AA6040, AA6041, AA6042, AA6043, AA6151, AA6351, AA6351A, AA6451, AA6951, AA605 3. AA6055, AA6056, AA6156, AA6060, AA6160, AA6260, AA6360, AA6460, AA6460B, AA6560, AA6660, AA6061, AA6061A , AA6261, AA6361, AA6162, AA6262, AA6262A, AA6063, AA6063A, AA6463, AA6463A, AA6763, A6963, AA6064, AA6064A, AA6065, AA6066, AA6068, AA6069, AA6070, AA6081, AA6181, AA6181A, AA6082, AA6082A, AA6182, AA6091, or AA6092.

[0086] Non-limiting exemplary 7xxx series aluminum alloys for use in the methods described herein may include AA7011, AA7019, AA7020, AA7021, AA7039, AA7072, AA7075, AA7085, AA7108, AA7108A, AA7015, AA7017, AA7018, AA7019A, AA7024, AA7025, AA7028 ,AA7030,AA7031,AA7033,AA7035,AA7035A,AA7046,AA7046A,AA7003,AA7004,AA7005,AA70 09. AA7010, AA7011, AA7012, AA7014, AA7016, AA7116, AA7122, AA7023, AA7026, AA7029, AA71 29. AA7229, AA7032, AA7033, AA7034, AA7036, AA7136, AA7037, AA7040, AA7140, AA7041, AA7 049, AA7049A, AA7149, AA7204, AA7249, AA7349, AA7449, AA7050, AA7050A, AA7150, AA7250, A AA7055, AA7155, AA7255, AA7056, AA7060, AA7064, AA7065, AA7068, AA7168, AA7175, AA7475, AA7076, AA7178, AA7278, AA7278A, AA7081, AA7181, AA7185, AA7090, AA7093, AA7095, or AA7099.

[0087] Non-limiting exemplary 8xxx series aluminum alloys for use in the methods described herein may include AA8005, AA8006, AA8007, AA8008, AA8010, AA8011, AA8011A, AA8111, AA8211, AA8112, AA8014, AA8015, AA8016, AA8017, AA8018, AA8019, AA8020, AA8021A, AA8022, AA8023, AA8024, AA8025, AA8026, AA8027, AA8028, AA8029, AA8030, AA8031, AA8032, AA8033, AA8034, AA8035, AA8036, AA8037, AA8038, AA8039, AA8040, AA8041, AA8042, AA8043, AA8044, AA8045, AA8046, AA8047, AA8048, AA8049, AA8050, AA8051 1. AA8021A, AA8021B, AA8022, AA8023, AA8024, AA8025, AA8026, AA8030, AA8130, AA8040, AA8050, AA8150, AA8076, AA8076A, AA8176, AA8077, AA8177, AA8079, AA8090, AA8091, or AA8093.

[0088] Battery Parts

[0089] The aluminum alloy products described herein can be used in electronic applications. For example, the aluminum alloy products and methods described herein can be used to prepare current collectors and / or battery electrodes (eg, aluminum-containing electrodes), such as for use in lithium-ion batteries.

[0090] Figure 5 is a schematic diagram of an example lithium-ion battery cell 500 including a thin-gauge aluminum cathode current collector. The lithium-ion battery 500 includes: a first electrode 502, which may correspond to a cathode in some examples; and a second electrode 504, which may correspond to an anode in some examples. The first electrode 502 of the lithium-ion battery 500 includes a first current collector 520. In some examples, the first current collector 520 may include a thin-gauge 1xxx series aluminum alloy or a thin-gauge 8xxx series aluminum alloy. The first electrode 502 also includes a first active material 530, such as a cathode active material. The second electrode 504 of the lithium-ion battery 500 includes a second current collector 506 and a second active material 515, such as an anode active material. As shown, the second current collector 506 includes an alloy layer 505 (as a second current collector), such as an aluminum alloy layer or a copper alloy layer, and a coating 510. In some examples, the alloy layer 505 may include a thin-gauge 1xxx series aluminum alloy or a thin-gauge 8xxx series aluminum alloy. Although the above reference to the uncoated current collector 520 and the current collector 506 including the coating 510 is described Figure 5 The depicted lithium-ion battery 500, however, is not intended to be limiting, and one or both of the first current collector 520 and the second current collector 506 may or may not include a coating. Where the second current collector 506 does not include a coating, the second current collector may include, consist of, or consist essentially of an alloy layer 505.

[0091] The coating 510 can be used to prevent the material from directly contacting the alloy layer 505 of the second current collector 506 or the material of the first current collector 520. In some examples, the coating 510 can be used to block or otherwise prevent the transmission of certain materials, such as limiting those materials from contacting the thin gauge 1xxx series aluminum alloy or the thin gauge 8xxx series aluminum alloy. In some examples, the coating 510 can be used to prevent lithium or lithium ions from contacting the alloy layer 505. Optionally, the coating 510 can be conductive and allow electrons to be transferred to the thin gauge 1xxx series aluminum alloy or the thin gauge 8xxx series aluminum alloy. In some examples, the coating 510 can be a carbonaceous material. Examples of carbonaceous materials can include carbon black materials or Ketjen black materials.

[0092] The lithium-ion battery 500 also includes a separator and / or an electrolyte, as shown in component 535. The separator and / or the electrolyte can be used to prevent the first electrode active material and the second electrode active material from contacting each other, while still allowing ions to be transmitted through during charging or discharging. An exemplary separator can be or include a non-reactive porous material, such as a polymer film, such as polypropylene, poly(methyl methacrylate), or polyacrylonitrile. An example electrolyte can be or include an organic solvent, such as ethylene carbonate, dimethyl carbonate, or diethyl carbonate, or a solid or ceramic electrolyte. The electrolyte can include a dissolved lithium salt, such as LiPF6, LiBF4, or LiClO4, as well as other additives.

[0093] The lithium-ion battery 500 may be used or used as a component of other devices, such as portable electronic devices, mobile phones, tablet computers, etc. For example, the first current collector 520 and the second current collector 506 of the lithium-ion battery 500 may be positioned to communicate directly or indirectly with the electronic device or the circuit of the electronic device and receive or provide current.

[0094] In some examples, first current collector 520 may include a 1xxx series aluminum alloy or an 8xxx series aluminum alloy having a thickness of about 5 μm to about 12 μm. Optionally, first current collector 520 may have a thickness of about 7 μm to about 12 μm. Example thicknesses may include 5 μm to 5.1 μm, 5.1 μm to 5.2 μm, 5.2 μm to 5.3 μm, 5.3 μm to 5.4 μm, 5.4 μm to 5.5 μm, 5.5 μm to 5.6 μm, 5.6 μm to 5.7 μm, 5.7 μm to 5.8 μm, 5.8 μm to 5.9 μm, 5.9 μm to 6.0 μm, 6.0 μm to 6.1 μm, 6.1 μm to 6.2 μm, 6.2 μm to 6.3 μm, 6.3 μm to 6.4 μm, 6.4 μm to 6.5 μm, 6.5 μm to 6.6 μm, 6.6 μm to 6.7 μm, 6.7 μm to 6.8 μm. .8μm, 6.8μm to 6.9μm, 6.9μm to 7.0μm, 7μm to 7.1μm, 7.1μm to 7.2μm, 7.2μm to 7.3μm, 7.3μm to 7.4μm, 7.4μm to 7.5μm, 7.5μm to 7.6μm, 7.6μm to 7.7μm, 7.7μm to 7.8μm, 7.8μm to 7.9μm, 7.9μm to 8μm, 8μm to 8.1μm, 8.1μm to 8.2μm, 8.2μm to 8.3μm, 8.3μm to 8.4μm, 8.4μm to 8.5μm, 8.5μm to 8.6μm, 8. 6μm to 8.7μm, 8.7μm to 8.8μm, 8.8μm to 8.9μm, 8.9μm to 9μm, 9μm to 9.1μm, 9.1μm to 9.2μm, 9.2μm to 9.3μm, 9.3μm to 9.4μm, 9.4μm to 9.5μm, 9.5μm to 9.6μm, 9.6μm to 9.7μm, 9.7μm to 9.8μm, 9.8μm to 9.9μm, 9.9μm to 10μm, 10μm to 10.1μm, 10.1μm to 10.2μm, 10.2μm to 10.3μm, 10.3μm to 10.4μm, 10 .4μm to 10.5μm, 10.5μm to 10.6μm, 10.6μm to 10.7μm, 10.7μm to 10.8μm, 10.8μm to 10.9μm, 10.9μm to 11μm, 11μm to 11.1μm, 11.1μm to 11.2μm, 11.2μm to 11.3μm, 11.3μm to 11.4μm, 11.4μm to 11.5μm, 11.5μm to 11.6μm, 11.6μm to 11.7μm, 11.7μm to 11.8μm, 11.8μm to 11.9μm, or 11.9μm to 12μm.

[0095] Example 8xxx series aluminum alloys may include AA8079, AA8090, or AA8077. In some examples, the first current collector 520 may contribute to improvements in specific capacity and / or energy density because the high iron content in the thin gauge 8xxx series aluminum alloy provides increased strength and / or reduced thickness of the current collector compared to other aluminum alloys (such as 1xxx series aluminum alloys). Additional elements (such as Fe, Si, Cu, or Zn) in thin gauge 8xxx series aluminum may also similarly contribute to improvements in specific capacity and energy density because improved strength properties allow for reduced thickness of the current collector.

[0096] Example percentages of Fe in thin gauge 8xxx series aluminum alloys may include up to 1.3 wt %, such as up to 1.2 wt %, up to 1.1 wt %, up to 1.0 wt %, up to 0.9 wt %, up to 0.8 wt %, up to 0.7 wt %, up to 0.6 wt %, up to 0.5 wt %, up to 0.4 wt %, up to 0.3 wt %, up to 0.2 wt %, up to 0.1 wt %, 0.1 to 1.3 wt %. %, 0.2 wt % to 0.3 wt %, 0.3 wt % to 0.4 wt %, 0.4 wt % to 0.5 wt %, 0.5 wt % to 0.6 wt %, 0.6 wt % to 0.7 wt %, 0.7 wt % to 0.8 wt %, 0.8 wt % to 0.9 wt %, 0.9 wt % to 1.0 wt %, 1.0 wt % to 1.1 wt %, 1.1 wt % to 1.2 wt %, or 1.2 wt % to 1.3 wt %.

[0097] Example percentages of Si in thin gauge 8xxx series aluminum alloys may include up to 0.3 wt %, up to 0.29 wt %, up to 0.28 wt %, up to 0.27 wt %, up to 0.26 wt %, up to 0.25 wt %, up to 0.24 wt %, up to 0.23 wt %, up to 0.22 wt %, up to 0.21 wt %, up to 0.20 wt %, up to 0.19 wt %, up to 0.18 wt %, up to 0.17 wt %, up to 0.16 wt %, up to 0.15 wt %, up to 0.14 wt %, up to 0.13 wt %, %, up to 0.12 wt %, up to 0.11 wt %, up to 0.10 wt %, up to 0.09 wt %, up to 0.08 wt %, up to 0.07 wt %, up to 0.06 wt %, up to 0.05 wt %, up to 0.04 wt %, up to 0.03 wt %, up to 0.02 wt %, up to 0.01 wt %, 0.05 wt % to 0.10 wt %, 0.10 wt % to 0.15 wt %, 0.15 wt % to 0.20 wt %, 0.20 wt % to 0.25 wt % or 0.25 wt % to 0.30 wt %.

[0098] Example percentages of Cu in thin gauge 8xxx series aluminum alloys may include up to 0.05 wt %, up to 0.04 wt %, up to 0.03 wt %, up to 0.02 wt %, up to 0.01 wt %, 0.01 wt % to 0.02 wt %, 0.02 wt % to 0.03 wt %, 0.03 wt % to 0.04 wt %, or 0.04 wt % to 0.05 wt %.

[0099] Example percentages of Zn in thin gauge 8xxx series aluminum alloys may include up to 0.10 wt %, up to 0.09 wt %, up to 0.08 wt %, up to 0.07 wt %, up to 0.06 wt %, up to 0.05 wt %, up to 0.04 wt %, up to 0.03 wt %, up to 0.02 wt %, up to 0.01 wt %, 0.01 wt % to 0.02 wt %, 0.02 wt % to 0.03 wt %, 0.03 wt % to 0.04 wt %, 0.04 wt % to 0.05 wt %, 0.05 wt % to 0.06 wt %, 0.06 wt % to 0.07 wt %, 0.07 wt % to 0.08 wt %, 0.08 wt % to 0.09 wt %, or 0.09 wt % to 0.10 wt %.

[0100] In some examples, production of the thin gauge 8xxx series aluminum alloy constituting the first current collector 520 can produce a shiny side and a matte side. The electrical conductivity between the first current collector 520 and the first active material 530 can be affected by the side of the thin gauge 8xxx series aluminum alloy facing the first active material 530. In some examples, arranging the first current collector 520 such that the matte side of the thin gauge 8xxx series aluminum alloy faces the first active material 530 can result in a higher electrical conductivity between the first current collector 520 and the first active material 530 than arranging the shiny side of the thin gauge 8xxx series aluminum alloy to face the first active material 530.

[0101] Example electrical conductivity between the first current collector 520 and the first active material 530 may be about 0.0275 S / m to about 0.0675 S / m, such as 0.0275 S / m to about 0.030 S / m, 0.030 S / m to 0.035 S / m, 0.035 S / m to 0.040 S / m, 0.040 S / m to 0.045 S / m, 0.045 S / m to 0.050 S / m, 0.050 S / m to 0.055 S / m, 0.055 S / m to 0.060 S / m, 0.060 S / m to 0.065 S / m, or 0.065 S / m to 0.0675 S / m.

[0102] In some examples, first current collector 520 can help maintain the specific capacity of battery 500 or electrode 502 above 90% of the initial specific capacity over a certain number of cycles. For example, the first current collector 520 can help maintain the specific capacity above 90% of the initial specific capacity over the following cycles: up to 3000 cycles, up to 2500 cycles, up to 2000 cycles, up to 1500 cycles, up to 1000 cycles, up to 900 cycles, up to 800 cycles, up to 700 cycles, up to 600 cycles, up to 500 cycles, up to 400 cycles, up to 300 cycles, up to 200 cycles, up to 100 cycles, 200 cycles to 3000 cycles, 500 cycles to 1000 cycles, 1000 cycles to 1500 cycles, 1500 cycles to 2000 cycles, 2000 cycles to 2500 cycles, or 2500 cycles to 3000 cycles.

[0103] Additionally, the first current collector 520 can help maintain the energy density of the battery 500 or electrode 502 above 90% of the initial energy density for a certain number of cycles, such as up to 3000 cycles or more. For example, the first current collector 520 can help maintain the energy density above 90% of the initial energy density for up to 3000 cycles, up to 2500 cycles, up to 2000 cycles, up to 1500 cycles, up to 1000 cycles, up to 900 cycles, up to 800 cycles, up to 700 cycles, up to 600 cycles, up to 500 cycles, up to 400 cycles, up to 300 cycles, up to 200 cycles, up to 100 cycles, 200 cycles to 3000 cycles, 500 cycles to 1000 cycles, 1000 cycles to 1500 cycles, 1500 cycles to 2000 cycles, 2000 cycles to 2500 cycles, or 2500 cycles to 3000 cycles.

[0104] In some examples, first current collector 520 and / or second current collector 506 or alloy layer 505 may be or include foil, such as rolled aluminum foil. In some examples, first current collector 520 may include or include recycled content aluminum alloy, such as produced using one or more of the following: 1xxx series aluminum alloy, 2xxx series aluminum alloy, 3xxx series aluminum alloy, 3xxx series aluminum alloy, 4xxx series aluminum alloy, 5xxx series aluminum alloy, 6xxx series aluminum alloy, or 7xxx series aluminum alloy. In some examples, first current collector 520 may include up to 50% recycled aluminum content. For example, the first current collector 520 may include 0% recycled aluminum composition, 1% recycled aluminum composition, 2% recycled aluminum composition, 3% recycled aluminum composition, 4% recycled aluminum composition, 5% recycled aluminum composition, 6% recycled aluminum composition, 7% recycled aluminum composition, 8% recycled aluminum composition, 9% recycled aluminum composition, 10% recycled aluminum composition, 11% recycled aluminum composition, 12% recycled aluminum composition, 13% recycled aluminum composition, 14% recycled aluminum composition, 15% recycled aluminum composition, 16% recycled aluminum composition, 17% recycled aluminum composition, 18% recycled aluminum composition, 19% recycled aluminum composition, 20% recycled aluminum composition, 21% recycled aluminum composition, 22% recycled aluminum composition, 23% recycled aluminum composition, 24% recycled aluminum composition, 25% recycled aluminum composition, 26% recycled aluminum composition, 27% recycled aluminum composition, 28% recycled aluminum composition, 29% recycled aluminum composition, 30% recycled aluminum composition, 31% recycled aluminum composition, 32% recycled aluminum composition, 33% recycled aluminum composition, 34% recycled aluminum composition, 35% recycled aluminum composition, 36% recycled aluminum composition, 37% recycled aluminum composition, 38% recycled aluminum composition, 39% recycled aluminum composition, 40% recycled aluminum composition, 41% recycled aluminum composition, 42% recycled aluminum composition, 43% recycled aluminum composition, 44% recycled aluminum composition, 45% recycled aluminum composition, 46% recycled aluminum composition, 47% recycled aluminum composition, 48% recycled aluminum composition, 49% recycled aluminum composition, 50% recycled aluminum composition, 51% recycled aluminum composition, 52% recycled aluminum composition, A recycled aluminum composition, a 26% recycled aluminum composition, a 27% recycled aluminum composition, a 28% recycled aluminum composition, a 29% recycled aluminum composition, a 30% recycled aluminum composition, a 31% recycled aluminum composition, a 32% recycled aluminum composition, a 33% recycled aluminum composition, a 34% recycled aluminum composition, a 35% recycled aluminum composition, a 36% recycled aluminum composition, a 37% recycled aluminum composition, a 38% recycled aluminum composition, a 39% recycled aluminum composition, a 40% recycled aluminum composition, a 41% recycled aluminum composition, a 42% recycled aluminum composition, a 43% recycled aluminum composition, a 44% recycled aluminum composition, a 45% recycled aluminum composition, a 46% recycled aluminum composition, a 47% recycled aluminum composition, a 48% recycled aluminum composition, a 49% recycled aluminum composition, or a 50% recycled aluminum composition.

[0105] The examples disclosed herein will be used to further illustrate various aspects of the present invention, but will not constitute any limitation to the present invention at the same time. On the contrary, it should be clearly understood that it may be necessary to resort to various embodiments, modifications and equivalents thereof that can be thought of by those skilled in the art after reading the description herein without departing from the spirit of the present invention. Unless otherwise stated, the examples and embodiments described herein may also utilize conventional procedures. Some programs are described herein for illustrative purposes.

[0106] Example 1

[0107] In this series of experiments, aluminum substrates (also referred to herein as cathode current collectors) were examined for their suitability for producing cathodes for lithium-ion batteries. Three substrates were tested: a cathode made of a current collector comprising AA8079 with a thickness of 7 μm and coated with a cathode active material on the matte side; a cathode made of a current collector comprising AA8079 with a thickness of 7 μm and coated with a cathode active material on the flash side; and a conventional cathode made of a current collector comprising AA1085 with a thickness of 16 μm and coated with a cathode active material on the matte side. To this end, the current collector substrate was coated with a suspension of active material (NMC-622), a conductive material, and a binder in a discontinuous process. The coating was completed on one side of the current collector substrate. Because the current collector substrate has a matte side (e.g., a "rough" side) and a flash side (e.g., a "smooth" side) due to its production, the effect of the roughness of the aluminum current collector substrate on the cathode was studied. In addition, the conductivity, coating adhesion, and discharge capacity achieved using various current collector substrates were also examined.

[0108] The compositions of the coatings on the substrates are depicted in Table 1 below.

[0109] Table 1

[0110]

[0111] A dissolver (Dispermat CA, VMA-Getzmann) was used to produce the suspension. Table 2 depicts the dispersion parameters.

[0112] Table 2

[0113]

[0114] After dispersion, the suspension was degassed under reduced pressure for 15 minutes. The substrate was coated discontinuously under a film coater (ZAA2300, Zehntner Testing Instruments) with the goal of obtaining 15.8 mg / cm 2 After coating, the cathode was compressed to 3 g / cm using a calender (GKL 400, Saueressig GmbH & Co. KG). 3 density.

[0115] Figure 6600a depicts an example pull-out test for a thin gauge aluminum alloy substrate 604. The bond strength of the aluminum alloy substrate 604 is determined by performing a pull-out test on a Z020 material testing machine from Zwick GmbH. The aluminum alloy substrate 604 is first pressed between two sample holders 606 with a defined force, and the sample holders are covered with tape 608. The sample holders 606 are then pulled apart while the force is measured. The bond strength is determined by the maximum tension and the force area. Using the pull-out test, different failure mechanisms can occur on the coating 602 on the aluminum alloy substrate 604. The basic section 600a depicts the aluminum alloy substrate 604 before the pull-out test. The basic sections 600b, 600c, and 600d depict the failure mechanisms after the pull-out test. The basic section 600b depicts the cohesive failure within the coating 602, because the coating 602 can be detected on the tape 608 and the aluminum alloy substrate 604. The basic section 600c depicts the bond failure in the case where a blank film can be detected after the pull-out test. Base portion 600d depicts tape failure in the event that tape 608 fails during testing.

[0116] To investigate the conductivity of the cathode, the cathode was pressed together with a force of 40 N in a sample holder 606 on a Z020 testing machine from Zwick GmbH. The RESISTOMAT 2329 resistance measuring device from GmbH & Co KG determines the voltage drop in a sample at a constant current. Fig. 9 The results of the conductivity tests are described.

[0117] Figure 7 700 is a graph of an example test process for a battery cell including a thin gauge aluminum alloy as a cathode current collector. Graph 700 depicts example capacities at different currents. The charge and discharge rates are shown as bars, and the discharge capacity is shown as a black curve. The cell was subjected to an activation / formation process at C / 10 for three cycles. The load-dependent performance was then checked in a C-rate test. Here, C-rates of 2, 3, 4, and 5C were used. 400 cycles were then completed at 1C, followed by a second C-rate test.

[0118] Figure 8 is a graph 800 depicting the bond strength obtained from pull-off tests on thin gauge aluminum alloy substrates. Graph 800 compares the bond strength in MPa of a 7 μm thick cathode coated on the shiny side versus the matte side. Figure 8The depicted bond strengths do not show much difference between the shiny and matte sides, but the failure modes after the pull-out test provide information about the underlying mechanisms. For example, the samples coated on the matte side show little to no bond failure and mainly cohesive failures. In the samples coated on the shiny side, bond failures are significantly more common. The bond strength of the coating on the cathode is therefore determined to be higher on the matte side of the aluminum alloy substrate.

[0119] Fig. 9 900 is a graph depicting the specific conductivity of a battery cell including a thin gauge aluminum alloy substrate as a cathode current collector. Graph 900 compares the specific conductivity in S / cm of a cell including a 7 μm thick cathode current collector coated on the flash side and the matte side. The specific conductivity of the cell with the cathode current collector coated on the matte side is almost twice as high as the specific conductivity of the cell with the cathode current collector coated on the flash side. However, the measurements include a significant standard deviation. The increase in the specific conductivity of the cell with the cathode current collector coated on the matte side may be due to a reduction in the interfacial resistance between the cathode current collector and the coating.

[0120] Fig.10 1 is a graph 1000 depicting the discharge specific capacity obtained by cycling a battery cell including a thin gauge aluminum alloy substrate as a cathode current collector. The cell was cycled for a minimum of 4 weeks to cover the formation, the first C-rate test, and most of the long-term cycling portion. Graph 1000 depicts the mean of the discharge specific capacity as a function of the cycle period for the following cells: a cell including a 7 μm thick cathode current collector coated on the matte side; a cell including a 7 μm thick cathode current collector coated on the flash side; and a cell including a 16 μm thick cathode current collector coated on the matte side. The 16 μm thick cathode current collector may correspond to a conventional cathode current collector having a conventional thickness as a reference. The cell including the 7 μm thick cathode current collector exhibits a significantly more stable capacity than the cell including the 16 μm thick cathode current collector, but the initial capacity is lower. Starting from about 225 cycles, the cell including the 7 μm thick cathode current collector exhibits a higher specific capacity than the cell including the 16 μm thick cathode current collector.

[0121] Fig.11 1100 is a graph depicting the specific discharge capacity obtained during C-rate testing of battery cells including a thin gauge aluminum alloy substrate as a cathode current collector. The cells including a 16 μm thick cathode current collector exhibited higher specific discharge capacity, especially at medium C-rates of 2C and 3C, followed by the cells including a 7 μm thick cathode current collector. As the C-rate increases, the difference between the measured values ​​decreases. This may be due to the increasing limitation of ion transport within the cathode at high currents.

[0122] Fig.121200 is a graph depicting the resulting energy density levels at the cathode level during a cycle test of a battery cell including a thin gauge aluminum alloy substrate as a cathode current collector. For this example, the energy during discharge is normalized to the mass of the cathode. Due to the lower basis weight of the thin gauge aluminum alloy cathode current collector, the cell including a 7 μm thick cathode current collector exhibits a higher energy density than the cell including a 16 μm thick cathode current collector throughout the duration of the cycle test.

[0123] Fig.13 is a graph 1300 depicting the resulting energy density levels at the cathode level during C-rate testing of battery cells including a thin gauge aluminum alloy substrate as a cathode current collector. If the discharge energy at the cathode level is considered during the C-rate testing, the difference between the cell including a 7 μm thick cathode current collector and the cell including a 16 μm thick cathode current collector is smaller than if the specific capacity is considered.

[0124] In summary, the coating on the cathode current collector has good adhesion at over 2.5 MPa. The conductivity of the cathode coated on the matte side of the current collector is significantly higher than the conductivity of the cathode coated on the flash side of the current collector. Both the discharge specific capacity and energy density at the cathode level are slightly higher for the cathode coated on the matte side of the current collector. The cell with a 7 μm thick cathode current collector provides higher energy density and higher life cycle or cycle stability compared to the cell with a 16 μm thick cathode current collector (see Fig.10 ).

[0125] Illustrative aspects

[0126] As used below, any reference to a series of aspects (e.g., “Aspects 1 to 4”) or an unlisted group of aspects (e.g., “any previous or subsequent aspect”) should be understood as a separate reference to each of those aspects (e.g., “Aspects 1 to 4” should be understood as “Aspect 1, Aspect 2, Aspect 3, or Aspect 4”).

[0127] Aspect 1 is a battery component comprising: a cathode current collector comprising a 1xxx series aluminum alloy or an 8xxx series aluminum alloy, wherein the cathode current collector has a thickness of 5 μm to 12 μm.

[0128] Aspect 2 is the battery component of any preceding or subsequent aspect, further comprising: an active material layer disposed on at least a portion of the cathode current collector.

[0129] Aspect 3 is a battery component of any previous or subsequent aspect, wherein the side of the 1xxx series aluminum alloy or the 8xxx series aluminum alloy facing the active material layer is a flash side, or wherein the surface of the 1xxx series aluminum alloy or the 8xxx series aluminum alloy in contact with the active material layer has a flash surface finish.

[0130] Aspect 4 is a battery component of any previous or subsequent aspect, wherein the side of the 1xxx series aluminum alloy or the 8xxx series aluminum alloy facing the active material layer is a matte side, or wherein the surface of the 1xxx series aluminum alloy or the 8xxx series aluminum alloy in contact with the active material layer has a matte surface finish.

[0131] Aspect 5 is the battery component of any previous or subsequent aspect, wherein the active material layer is disposed on both sides of the 1xxx series aluminum alloy or the 8xxx series aluminum alloy.

[0132] Aspect 6 is the battery component of any previous or subsequent aspect, wherein both sides of the 1xxx series aluminum alloy or the 8xxx series aluminum alloy have a matte surface finish.

[0133] Aspect 7 is the battery component of any preceding or subsequent aspect, wherein the electrical conductivity between the active material layer and the cathode current collector ranges from 0.0275 S / m to 0.0675 S / m.

[0134] Aspect 8 is the battery component of any preceding or subsequent aspect, wherein the electrical conductivity between the active material layer and the cathode current collector ranges from 0.04 S / m to 0.0675 S / m.

[0135] Aspect 9 is the battery component of any preceding or subsequent aspect, wherein the cathode current collector has a thickness of 7 μm to 12 μm.

[0136] Aspect 10 is the battery component of any preceding or subsequent aspect, wherein the cathode current collector has a thickness of 7 μm to 10 μm.

[0137] Aspect 11 is the battery component of any preceding or subsequent aspect, wherein the cathode current collector comprises a recycled content aluminum alloy.

[0138] Aspect 12 is the battery component of any preceding or subsequent aspect, wherein the cathode current collector comprises up to 50% recycled aluminum content.

[0139] Aspect 13 is the battery component of any preceding or subsequent aspect, wherein the battery component maintains the specific capacity above 90% of the initial specific capacity for up to 3000 cycles.

[0140] Aspect 14 is the battery component of any preceding or subsequent aspect, wherein the battery component maintains energy density above 90% of the initial energy density for up to 3000 cycles.

[0141] Aspect 15 is the battery component of any preceding or subsequent aspect, further comprising: a conductive layer disposed on at least a portion of a surface of the cathode current collector.

[0142] Aspect 16 is the battery component of any preceding or subsequent aspect, wherein the conductive layer is a carbonaceous material.

[0143] Aspect 17 is the battery component of any preceding or subsequent aspect, wherein the cathode current collector comprises the 8xxx series aluminum alloy, the 8xxx series aluminum alloy comprising Al and at least one of Si, Cu, Fe, or Zn.

[0144] Aspect 18 is the battery component of any preceding or subsequent aspect, wherein the 8xxx series aluminum alloy comprises up to 0.3 wt. % Si, up to 0.05 wt. % Cu, up to 1.3 wt. % Fe, and up to 0.10 wt. % Zn.

[0145] Aspect 19 is the battery component of any preceding or subsequent aspect, wherein the cathode current collector comprises the 8xxx series aluminum alloy, and wherein the 8xxx series aluminum alloy is a 8079 series aluminum alloy, a 8090 series aluminum alloy, or a 8077 series aluminum alloy.

[0146] Aspect 20 is a method for manufacturing a battery component, the method comprising: providing a cathode current collector comprising a 1xxx series aluminum alloy or an 8xxx series aluminum alloy, wherein the cathode current collector has a thickness of 5 μm to 12 μm; and applying a cathode active material on a surface of the cathode current collector.

[0147] Aspect 21 is the method of any preceding or subsequent aspect, further comprising subjecting the cathode current collector to a coating process to form a conductive layer.

[0148] Aspect 22 is the method of any preceding or subsequent aspect, wherein the conductive layer is a carbonaceous material.

[0149] Aspect 23 is the method of any preceding or subsequent aspect, wherein the cathode current collector comprises the battery component or metal product of any preceding or subsequent aspect.

[0150] Aspect 24 is a battery component of any preceding or subsequent aspect, wherein the battery component is prepared using the method of any preceding or subsequent aspect.

[0151] Aspect 25 is a battery comprising the battery component or metal product of any preceding or subsequent aspect.

[0152] Aspect 26 is the battery of any previous or subsequent aspect, comprising: an anode; and a cathode, wherein the cathode comprises: the battery component or metal product of any previous or subsequent aspect as a cathode current collector; and a cathode active material in contact with the cathode current collector.

[0153] Aspect 27 is the battery of any preceding or subsequent aspect, further comprising an electrolyte positioned between the cathode and the anode.

[0154] Aspect 28 is the battery of any preceding or subsequent aspect, wherein the electrolyte is a liquid electrolyte or a solid electrolyte.

[0155] Aspect 29 is a method for preparing aluminum foil, the method comprising: feeding three or more aluminum alloy sheets to a rolling mill stand; co-rolling the three or more aluminum alloy sheets using the rolling mill stand to reduce the specifications of the three or more aluminum alloy sheets and produce three or more aluminum alloy foils, wherein the top surface of at least one of the aluminum alloy sheets has a matte surface finish, and the bottom surface has a matte surface finish.

[0156] Aspect 30 is the method of any preceding or subsequent aspect, wherein the three or more aluminum alloy sheets comprise three aluminum alloy sheets, and wherein the three or more aluminum alloy foils comprise three aluminum alloy foils.

[0157] Aspect 31 is the method of any preceding or subsequent aspect, wherein the three or more aluminum alloy sheets include four aluminum alloy sheets, and wherein the three or more aluminum alloy foils include four aluminum alloy foils.

[0158] Aspect 32 is the method of any preceding or subsequent aspect, wherein the three or more aluminum alloy sheets all comprise the same aluminum alloy.

[0159] Aspect 33 is the method of any preceding or subsequent aspect, wherein the at least one of the three or more aluminum alloy sheets comprises an aluminum alloy that is different from at least one other aluminum alloy sheet.

[0160] Aspect 34 is the method of any preceding or subsequent aspect, wherein the three or more aluminum alloy sheets comprise a 1xxx series aluminum alloy or an 8xxx series aluminum alloy.

[0161] Aspect 35 is the method of any preceding or subsequent aspect, wherein the three or more aluminum alloy sheets all have the same thickness, or wherein the three or more aluminum alloy foils all have the same thickness.

[0162] Aspect 36 is the method of any previous or subsequent aspect, wherein the at least one of the three or more aluminum alloy sheets has a different thickness than at least one other aluminum alloy sheet, or wherein at least one of the three or more aluminum alloy foils has a different thickness than at least one other aluminum alloy foil.

[0163] Aspect 37 is the method of any preceding or subsequent aspect, further comprising applying a coating to the top surface or the bottom surface of at least one of the aluminum alloy sheets having the top surface having the matte surface finish and the bottom surface having the matte surface finish.

[0164] Aspect 38 is the method of any preceding or subsequent aspect, wherein the coating comprises a layer of active material for a battery.

[0165] Aspect 39 is a method of any previous aspect, further comprising adjusting one or more rolling parameters to control the gauge thickness of the three or more aluminum alloy foils, wherein the rolling parameters include a first feed rate of a first aluminum alloy sheet among the three or more aluminum alloy sheets, a second feed rate of a second aluminum alloy sheet among the three or more aluminum alloy sheets, a third feed rate of a third aluminum alloy sheet among the three or more aluminum alloy sheets, a pressure applied to the three or more aluminum alloy sheets by the rolling mill stand, or a rolling speed of the rolling mill stand.

[0166] Aspect 40 is a metal product comprising an aluminum alloy foil having a top surface with a matte surface finish and a bottom surface with a matte surface finish.

[0167] Aspect 41 is the metal product of any preceding or subsequent aspect, wherein the specular gloss level of the matte surface finish is 30% or less, 20% or less, or 10% or less.

[0168] Aspect 42 is the metal product of any preceding or subsequent aspect, wherein the matte surface finish has a surface roughness of 0.1 μm to 0.5 μm.

[0169] Aspect 43 is the metal product of any preceding or subsequent aspect, wherein the matte surface finish is characteristic of processing by rolling against another aluminum alloy foil surface.

[0170] Aspect 44 is the metal product of any preceding or subsequent aspect, wherein the aluminum alloy foil is a rolled aluminum alloy foil, or wherein the aluminum alloy foil has an elongated grain structure characteristic of a rolling process.

[0171] Aspect 45 is the metal product of any preceding or subsequent aspect, wherein the aluminum alloy foil has a thickness of 5 μm to 200 μm.

[0172] Aspect 46 is the metal product of any preceding or subsequent aspect, wherein the aluminum alloy foil has a thickness of 5 μm to 12 μm.

[0173] Aspect 47 is the metal product of any preceding or subsequent aspect, further comprising a coating disposed on at least a portion of the aluminum alloy foil.

[0174] Aspect 48 is the metal product of any preceding or subsequent aspect, wherein the coating comprises a layer of active material for a battery.

[0175] Aspect 49 is the metal product of any preceding or subsequent aspect, wherein the aluminum alloy foil comprises a 1xxx series aluminum alloy or an 8xxx series aluminum alloy.

[0176] Aspect 50 is the metal product of any preceding or subsequent aspect, wherein the aluminum alloy foil comprises a recycled content aluminum alloy.

[0177] Aspect 51 is the metal product of any preceding or subsequent aspect, wherein the aluminum alloy foil comprises an 8xxx series aluminum alloy comprising Al and at least one of Si, Cu, Fe, or Zn.

[0178] Aspect 52 is the metal product of any preceding or subsequent aspect, wherein the 8xxx series aluminum alloy includes up to 0.3 wt. % Si, up to 0.05 wt. % Cu, up to 1.3 wt. % Fe, or up to 0.10 wt. % Zn.

[0179] Aspect 53 is the metal product of any previous aspect, wherein the 8xxx series aluminum alloy is a 8079 series aluminum alloy, a 8090 series aluminum alloy, or a 8077 series aluminum alloy.

[0180] All patents and publications cited herein are incorporated by reference in their entirety. The foregoing description of the embodiments, including the illustrated embodiments, is presented for illustration and description purposes only and is not intended to be exhaustive or limited to the precise forms disclosed. Numerous modifications, variations and uses of the present invention will be apparent to those skilled in the art.

Claims

1. A battery component, comprising: a cathode current collector comprising a 1xxx series aluminum alloy or an 8xxx series aluminum alloy, The thickness of the cathode current collector is 5 μm to 12 μm.

2. The battery component according to claim 1, further comprising: An active material layer is disposed on at least a portion of the cathode current collector.

3. The battery component of claim 2, wherein the side of the 1xxx series aluminum alloy or the 8xxx series aluminum alloy that faces the active material layer is a flash side, or wherein the surface of the 1xxx series aluminum alloy or the 8xxx series aluminum alloy that contacts the active material layer has a flash surface finish.

4. The battery component of claim 2, wherein the side of the 1xxx series aluminum alloy or the 8xxx series aluminum alloy that faces the active material layer is a matte side, or wherein the surface of the 1xxx series aluminum alloy or the 8xxx series aluminum alloy that contacts the active material layer has a matte surface finish. 5 . The battery component of claim 2 , wherein the active material layer is disposed on both sides of the 1xxx series aluminum alloy or the 8xxx series aluminum alloy.

6. The battery component of claim 5, wherein both sides of the 1xxx series aluminum alloy or the 8xxx series aluminum alloy have a matte surface finish. 7 . The battery component of claim 2 , wherein the electrical conductivity between the active material layer and the cathode current collector ranges from 0.0275 S / m to 0.0675 S / m.

8. The battery component of claim 2, wherein the electrical conductivity between the active material layer and the cathode current collector ranges from 0.04 S / m to 0.0675 S / m. 9 . The battery component of claim 1 , wherein the cathode current collector has a thickness of 7 μm to 12 μm. 10 . The battery component of claim 1 , wherein the cathode current collector has a thickness of 7 μm to 10 μm.

11. The battery component of claim 1, wherein the cathode current collector comprises a recycled content aluminum alloy.

12. The battery component of claim 11, wherein the cathode current collector comprises up to 50% recycled aluminum content.

13. The battery component of claim 1, wherein the battery component maintains a specific capacity greater than 90% of the initial specific capacity for up to 3000 cycles.

14. The battery component of claim 1, wherein the battery component maintains energy density greater than 90% of initial energy density for up to 3000 cycles.

15. The battery component of claim 1, further comprising: A conductive layer is disposed on at least a portion of a surface of the cathode current collector.

16. The battery component of claim 15, wherein the conductive layer is a carbonaceous material.

17. The battery component of claim 1, wherein the cathode current collector comprises the 8xxx series aluminum alloy comprising Al and at least one of Si, Cu, Fe, or Zn.

18. The battery component of claim 17, wherein the 8xxx series aluminum alloy comprises up to 0.3 wt. % Si, up to 0.05 wt. % Cu, up to 1.3 wt. % Fe, and up to 0.10 wt. % Zn.

19. The battery component of claim 1, wherein the cathode current collector comprises the 8xxx series aluminum alloy, and wherein the 8xxx series aluminum alloy is a 8079 series aluminum alloy, a 8090 series aluminum alloy, or a 8077 series aluminum alloy.

20. A method of manufacturing a battery component, the method comprising: Providing a cathode current collector, the cathode current collector comprising a 1xxx series aluminum alloy or an 8xxx series aluminum alloy, wherein the cathode current collector has a thickness of 5 μm to 12 μm; as well as A cathode active material is applied on the surface of the cathode current collector.

21. The method of claim 20, further comprising: The cathode current collector is subjected to a coating process to form a conductive layer.

22. The method of claim 21, wherein the conductive layer is a carbonaceous material.

23. The method of claim 20, wherein the cathode current collector comprises a battery component as claimed in any one of claims 1 to 19.

24. The battery component according to any one of claims 1 to 19, prepared using the method according to any one of claims 20 to 23.

25. A battery comprising the battery component according to any one of claims 1 to 19 or 24.

26. The battery of claim 25, comprising: anode; as well as a cathode, wherein the cathode comprises The battery component according to any one of claims 1 to 19 or 24, which is used as a cathode current collector; as well as A cathode active material is in contact with the cathode current collector.

27. The battery of claim 26, further comprising an electrolyte positioned between the cathode and the anode.

28. The battery of claim 27, wherein the electrolyte is a liquid electrolyte or a solid electrolyte.

29. A method for preparing aluminum foil, the method comprising: feeding three or more aluminum alloy sheets into a rolling mill stand; The three or more aluminum alloy sheets are co-rolled using the rolling mill stand to reduce the gauge of the three or more aluminum alloy sheets and produce three or more aluminum alloy foils, wherein a top surface of at least one of the aluminum alloy sheets has a matte surface finish and a bottom surface has a matte surface finish.

30. The method of claim 29, wherein the three or more aluminum alloy sheets comprise three aluminum alloy sheets, and wherein the three or more aluminum alloy foils comprise three aluminum alloy foils.

31. The method of claim 29, wherein the three or more aluminum alloy sheets include four aluminum alloy sheets, and wherein the three or more aluminum alloy foils include four aluminum alloy foils.

32. The method of claim 29, wherein the three or more aluminum alloy sheets all comprise the same aluminum alloy.

33. The method of claim 29, wherein the at least one of the three or more aluminum alloy sheets comprises an aluminum alloy that is different from at least one other aluminum alloy sheet.

34. The method of claim 29, wherein the three or more aluminum alloy sheets comprise a 1xxx series aluminum alloy or an 8xxx series aluminum alloy.

35. The method of claim 29, wherein the three or more aluminum alloy sheets all have the same thickness, or wherein the three or more aluminum alloy foils all have the same thickness.

36. The method of claim 29, wherein the at least one of the three or more aluminum alloy sheets has a different thickness than at least one other aluminum alloy sheet, or wherein at least one of the three or more aluminum alloy foils has a different thickness than at least one other aluminum alloy foil.

37. The method of claim 29, further comprising applying a coating to the top surface or the bottom surface of at least one of the aluminum alloy sheets having the top surface having the matte surface finish and the bottom surface having the matte surface finish.

38. The method of claim 37, wherein the coating comprises a layer of active material for a battery.

39. The method of claim 29, further comprising adjusting one or more rolling parameters to control the gauge thickness of the three or more aluminum alloy foils, wherein the rolling parameters include a first feed rate of a first aluminum alloy sheet among the three or more aluminum alloy sheets, a second feed rate of a second aluminum alloy sheet among the three or more aluminum alloy sheets, a third feed rate of a third aluminum alloy sheet among the three or more aluminum alloy sheets, a pressure applied by the rolling mill stand to the three or more aluminum alloy sheets, or a rolling speed of the rolling mill stand.

40. A metal product comprising: An aluminum alloy foil having a top surface with a matte surface finish and a bottom surface with a matte surface finish.

41. The metal product of claim 40, wherein the matte surface finish has a specular gloss level of 30% or less, 20% or less, or 10% or less.

42. The metal product of claim 40, wherein the matte surface finish has a surface roughness of 0.1 μm to 0.5 μm.

43. The metal product of claim 40, wherein the matte surface finish is characteristic of a rolling process performed against another aluminum alloy foil surface.

44. The metal product of claim 40, wherein the aluminum alloy foil is a rolled aluminum alloy foil, or wherein the aluminum alloy foil has an elongated grain structure characteristic of a rolling process.

45. The metal product of claim 40, wherein the aluminum alloy foil has a thickness of 5 μm to 200 μm.

46. ​​The metal product of claim 40, wherein the aluminum alloy foil has a thickness of 5 μm to 12 μm.

47. The metal product of claim 40, further comprising a coating disposed on at least a portion of the aluminum alloy foil.

48. The metal product of claim 47, wherein the coating comprises a layer of active material for a battery.

49. The metal product of claim 40, wherein the aluminum alloy foil comprises a 1xxx series aluminum alloy or an 8xxx series aluminum alloy.

50. The metal product of claim 40, wherein the aluminum alloy foil comprises a recycled content aluminum alloy.

51. The metal product of claim 40, wherein the aluminum alloy foil comprises an 8xxx series aluminum alloy comprising Al and at least one of Si, Cu, Fe, or Zn.

52. The metal product of claim 51, wherein the 8xxx series aluminum alloy includes up to 0.3 wt. % Si, up to 0.05 wt. % Cu, up to 1.3 wt. % Fe, or up to 0.10 wt. % Zn.

53. The metal product of claim 51, wherein the 8xxx series aluminum alloy is a 8079 series aluminum alloy, a 8090 series aluminum alloy, or a 8077 series aluminum alloy.